Water dispersion composition, method for producing said water dispersion composition, and acid-modified ethylene / α-olefin copolymer

JP7645911B2Active Publication Date: 2025-03-14MITSUI CHEMICALS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022575670
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-18
Filing Date
2022-01-18
Publication Date
2025-03-14
Estimated Expiration
2042-01-18

AI Technical Summary

Benefits of technology

【0010】 本発明の水分散体は、水分散体を形成するエチレン·α-オレフィン共重合体酸変性物(B)の粒径が小さくなり、より分散性が向上するので、エマルションが分離しづらくなることで長期安定性が向上し、また、粒子同士の相互作用が増し粘度が高くなることで基材への密着性が向上し、また、液だれも抑制されることから基材などへのコート性も向上する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645911000001
    Figure 0007645911000001
  • Figure 0007645911000002
    Figure 0007645911000002
  • Figure 0007645911000003
    Figure 0007645911000003
Patent Text Reader

Abstract

The purpose of the present invention is to obtain an aqueous dispersion in which dispersibility of an acid-modified ethylene·α-olefin copolymer is further improved and which exhibits excellent coatability on a substrate. The present invention relates to an aqueous dispersion composition that is characterized by: by being an acid-modified product of an ethylene·α-olefin copolymer (A) that satisfies (A1) to (A6); and by containing 0.01-50 mass% of an acid-modified ethylene·α-olefin copolymer (B) which satisfies (B1) to (B5). (A1) The content of ethylene units falls within the range 30-85 mol%. (A2) The kinematic viscosity at 100ºC falls within the range 10-5000 mm2 / s. (A3) The weight average molecular weight, as measured in terms of polystyrene using gel permeation chromatography (GPC), falls within the range 1000-50,000. (A4) The molecular weight distribution of molecular weights (Mw / Mn), as measured in terms of polystyrene using gel permeation chromatography (GPC), is 2.5 or less. (A5) The value of B represented in formula [1] is 1.1 or more. [In formula [1], PE denotes the molar ratio of ethylene units, PO denotes the molar ratio of α-olefin units, and POE denotes the molar ratio of ethylene·α-olefin chains relative to the total amount of dyad chains.] (A6) The amount of unsaturated bonds, as measured using 1H-NMR, is less than 0.5 per 1000 carbon atoms. (B1) The acid value falls within the range 1-300 mg KOH / g. (B2) The apparent viscosity at 150ºC falls within the range 1-1000 cPs. (B3) The weight average molecular weight, as measured in terms of polystyrene using gel permeation chromatography (GPC), falls within the range 1000-50,000. (B4) The molecular weight distribution of molecular weights (Mw / Mn), as measured in terms of polystyrene using gel permeation chromatography (GPC), is 2.5 or less. (B5) The weight percentage of unreacted molecules, as measured using high performance liquid chromatography (HPLC), is 59% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous dispersion composition having excellent dispersibility, a method for producing the aqueous dispersion composition, and an acid-modified ethylene / α-olefin copolymer. [Background technology]

[0002] Conventionally, in various industrial fields, it is known to bond substrates such as plastic films, vapor-deposited films, metal foils, papers, nonwoven fabrics, etc., together, or to bond a substrate to another adherend, by heat and pressure (i.e., heat sealing). In heat sealing, a method is usually used in which the substrates are bonded together, or the substrate is bonded to an adherend, directly, but in order to improve the heat sealability between the substrate and the adherend, a method is also used in which a heat seal agent (adhesive) layer is formed on the substrate in advance, and the substrates are bonded together, or the substrate is bonded to another adherend, via the adhesive layer.

[0003] As an adhesive used in such a heat sealant, for example, an aqueous dispersion containing at least one type of high crystallinity polyolefin having a crystallinity of more than 50%, at least one type of dispersant, and water has been proposed (see, for example, Patent Document 1).

[0004] The applicant has found that an aqueous dispersion composition containing at least one selected from a specific ethylene-α-olefin copolymer (A) and an acid-modified form (B) of the (A) in the range of 0.01 to 50 mass % improves the dispersibility of the acid-modified form (B) and the like, and proposed this in JP 2016-102157 A (Patent Document 2). However, depending on the application, an aqueous dispersion having even better dispersibility and excellent coatability on substrates and the like is required. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-52124 A [Patent Document 2] JP 2016-102157 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to obtain an aqueous dispersion of an acid-modified ethylene / α-olefin copolymer having improved dispersibility and excellent coatability onto substrates and the like. [Means for solving the problem]

[0007] The present inventors conducted various studies to obtain an aqueous dispersion with improved dispersibility, and as a result, they found that an ethylene-α-olefin copolymer, which is modified with an unsaturated carboxylic acid and its derivatives, is the most suitable for forming the aqueous dispersion. Things, among them , the modification rate is high, in other words, the content of unreacted molecules is low. thing It has been found that the above object can be achieved by using the above.

[0008] That is, the present invention provides an acid-modified ethylene-α-olefin copolymer (A) that satisfies the following (A1) to (A6): thing and the acid-modified ethylene / α-olefin copolymer satisfies the following (B1) to (B5). thing The present invention relates to an aqueous dispersion composition comprising (B) in an amount of 0.01 to 50% by mass. (A1) The content of ethylene units is in the range of 30 to 85 mol %. (A2) Kinematic viscosity at 100°C is 10 to 5,000 mm 2 / s range. (A3) The weight average molecular weight, as calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) is in the range of 1,000 to 50,000. (A4) The molecular weight distribution (Mw / Mn) measured by gel permeation chromatography (GPC) and calculated as polystyrene is 2.5 or less. (A5) The B value represented by the following formula [1] is 1.1 or more.

[0009]

number

[0010] The aqueous dispersion of the present invention is an acid-modified ethylene-α-olefin copolymer that forms an aqueous dispersion. thing As the particle size of (B) becomes smaller and its dispersibility improves, the emulsion becomes less likely to separate, improving its long-term stability. In addition, the interaction between particles increases, increasing the viscosity, improving adhesion to the substrate. Also, dripping is suppressed, improving the ability to coat the substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The aqueous dispersion composition of the present invention, the method for producing the aqueous dispersion composition, and the acid-modified ethylene / α-olefin copolymer are described in detail below. The aqueous dispersion composition of the present invention is a mixture of an ethylene-α-olefin copolymer (A) and an acid-modified ethylene-α-olefin copolymer (A) as described below. thing They contain (B). Hereinafter, they will be referred to as "component (A)" and "component (B)", respectively.

[0012] In this specification, a structural unit derived from a monomer is also referred to as a "monomer unit." [Ethylene-α-olefin copolymer (A)] The ethylene / α-olefin copolymer (A) that is the source of the acid-modified ethylene / α-olefin copolymer (B) that forms the aqueous dispersion of the present invention satisfies the following (A1) to (A6).

[0013] (A1) The content of ethylene units is in the range of 30 to 85 mol %. The content of ethylene units in component (A) is in the range of 30 to 85 mol%, preferably 40 to 70 mol%, particularly preferably 45 to 65 mol%. If the content is too far out of the above range, the copolymer will become crystalline, resulting in an increase in viscosity of the copolymer or becoming solid, which will deteriorate the dispersibility of the copolymer in water. If the content exceeds 85 mol%, the amount of tertiary carbon that is prone to decomposition reaction in the main chain will be reduced, and when the aqueous dispersion composition of the present invention is used as, for example, a mold release agent for die casting, oxidation degradation products generated by heat will be easily deposited on the surface of the mold, which is not preferable.

[0014] The content of ethylene units in component (A) was calculated according to the method described in "Polymer Analysis Handbook" (Asakura Publishing, 2008, first edition, pp. 184-211). 13 It is measured by C-NMR. It is also possible to measure the content of a sample determined by this method using Fourier transform infrared spectroscopy (FT-IR) as a known sample. The total content of all monomer units is taken as 100 mol%.

[0015] (A2) Kinematic viscosity at 100°C is 10 to 5,000 mm2 / s range. The kinetic viscosity of component (A) is a value measured by the method described in JIS K2283. The kinetic viscosity of component (A) at 100°C is 10 to 5,000 mm 2 / s, preferably in the range of 10 to 2,500 mm 2 / s, more preferably 15 to 2,500 mm 2 / s, particularly preferably 15 to 500 mm 2 / s. If the kinetic viscosity is excessively below the above range, the copolymer contains a large amount of easily volatile components, which makes it easy to ignite and deteriorates the storage stability, and the evaporation loss in the aqueous dispersion increases, and when used as a die-casting release agent, for example, the high molecular weight components that tend to adhere to the die decrease, which are undesirable. If the kinetic viscosity is excessively above the above range, the viscosity of the copolymer increases, making it difficult to disperse uniformly in water.

[0016] (A3) The weight average molecular weight is in the range of 1,000 to 50,000. The weight average molecular weight (Mw) of component (A) is a value obtained by measuring by gel permeation chromatography (GPC) according to the method described later and converting it into standard polystyrene. The weight average molecular weight (Mw) of component (A) is in the range of 1,000 to 50,000, preferably 1,500 to 30,000, more preferably 1,500 to 20,000, and particularly preferably 1,500 to 7,000. If Mw is excessively below the above range, it is undesirable that the copolymer contains a large amount of easily volatile components, which makes it easy to ignite and deteriorates storage stability, that the evaporation loss in the aqueous dispersion increases, and that, for example, when used as a die-casting release agent, the amount of high molecular weight components that easily adhere to the mold decreases. If Mw is excessively above the above range, the viscosity of the copolymer increases, making it difficult to disperse uniformly in water.

[0017] (A4) The molecular weight distribution is 2.5 or less. The molecular weight distribution of component (A) is measured by gel permeation chromatography (GPC) according to the method described below, and is calculated as the ratio (Mw / Mn) of the weight average molecular weight (Mw) obtained by standard polystyrene conversion to the number average molecular weight (Mn). The Mw / Mn of component (A) is 2.5 or less, preferably 2.3 or less, and more preferably 2.0 or less. When the molecular weight distribution excessively exceeds the above range, it means that the copolymer contains a large amount of low molecular weight components and high molecular weight components. When the copolymer contains a large amount of low molecular weight components, it is easily flammable due to the large amount of easily volatile components, which deteriorates the storage stability and increases the evaporation loss in the aqueous dispersion. When the copolymer contains a large amount of high molecular weight components, the viscosity of the copolymer increases, making it difficult to disperse uniformly in water.

[0018] (A5) The B value is 1.1 or more. The B value of component (A), represented by the following formula [1], is 1.1 or more, preferably 1.2 or more. There is no particular upper limit to the B value, but it is usually 2.0 or less.

[0019]

number

[0020] The B value is an index showing the randomness of the distribution of copolymerized monomer sequences in a copolymer, and is expressed by P in the above formula [1]. E , P O and P OE teeth, 13 The C-NMR spectrum can be measured and the value can be determined based on known literature such as the reports of JC Randal [Macromolecules, 15, 353 (1982)] and J. Ray [Macromolecules, 10, 773 (1977)], "Polymer Analysis Handbook" (Asakura Publishing, first edition, published in 2008, pp. 184-211).

[0021] The larger the B value, the fewer the chain structures of ethylene units and α-olefin units, the more uniform the distribution of ethylene units and α-olefin units, and the narrower the composition distribution of the copolymer. As a result, the larger the B value, the less likely component (A) will crystallize, and the less likely component (A) will increase in viscosity or become solid, and the less likely its dispersibility in water will deteriorate.

[0022] Specific conditions for measuring the B value are as described in the Examples. (A6) 1 The amount of unsaturated bonds measured by H-NMR is less than 0.5 per 1000 carbon atoms.

[0023] The molecule of component (A) has 1 The total number of double bonds derived from vinyl, vinylidene, di-substituted olefins, tri-substituted olefins, etc. (hereinafter also referred to as "unsaturated bond amount") measured by H-NMR is less than 0.5, preferably less than 0.3, more preferably less than 0.2, and particularly preferably less than 0.1 per 1000 carbon atoms. When the unsaturated bond amount is within this range, the heat resistance of component (A) is good. The specific measurement conditions for the unsaturated bond amount are as described in the examples.

[0024] It is preferable that the component (A) further satisfies the following (A7). (A7) No melting point is observed. It is preferable that component (A) has no observed melting point in differential scanning calorimetry (DSC). Here, "no observed melting point (Tm)" means that the heat of fusion (ΔH) (unit: J / g) measured by differential scanning calorimetry (DSC) is not substantially measured. "No substantially measured heat of fusion (ΔH)" means that no peak is observed in differential scanning calorimetry (DSC) or the observed heat of fusion is 1 J / g or less.

[0025] The melting point (Tm) and heat of fusion (ΔH) of component (A) are determined by performing differential scanning calorimetry (DSC) and analyzing the DSC curve with reference to JIS K7121 when the component is cooled to -100°C and then heated to 150°C at a heating rate of 10°C / min. If no melting point is observed, this means that component (A) has low crystallinity, does not increase in viscosity, does not become solid, and has excellent dispersibility in water.

[0026] Examples of the α-olefin that forms component (A) include linear or branched α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.

[0027] The α-olefin is preferably a linear or branched α-olefin having 3 to 10 carbon atoms, more preferably at least one selected from propylene, 1-butene, 1-hexene, and 1-octene, and most preferably propylene from the viewpoint of the fluidity of the aqueous dispersion composition using the resulting copolymer.

[0028] The α-olefins can be used alone or in combination of two or more. Also, the component (A) can be obtained by carrying out polymerization in the presence of at least one other monomer selected from a polar group-containing monomer, an aromatic vinyl compound, an alicyclic vinyl compound, and a cyclic olefin in the reaction system together with the α-olefin. The other monomer can be used in an amount of, for example, 20 parts by mass or less, preferably 10 parts by mass or less, based on 100 parts by mass of the total of ethylene and the α-olefin.

[0029] Examples of polar group-containing monomers include α,β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, fumaric acid, and maleic anhydride, and metal salts thereof such as sodium salts, α,β-unsaturated carboxylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, methyl methacrylate, and ethyl methacrylate, vinyl esters such as vinyl acetate and vinyl propionate, and unsaturated glycidyls such as glycidyl acrylate and glycidyl methacrylate.

[0030] Examples of aromatic vinyl compounds include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, methoxystyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylbenzyl acetate, hydroxystyrene, p-chlorostyrene, divinylbenzene, α-methylstyrene, and allylbenzene.

[0031] An example of the alicyclic vinyl compound is vinylcyclohexane. Examples of the cyclic olefin include cyclic olefins having 3 to 30 carbon atoms, preferably 3 to 20 carbon atoms, such as cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, and tetracyclododecene.

[0032] The component (A) may be used alone or in combination of two or more kinds, for example, two or more kinds of components (A) having different molecular weights and / or different monomer compositions may be used in combination.

[0033] The method for producing component (A) is not particularly limited, but includes a method using a vanadium catalyst containing a vanadium compound and an organoaluminum compound as described in JP-B-2-1163 and JP-B-2-7998. In addition, as a method for producing a copolymer with high polymerization activity, a method using a metallocene catalyst containing a metallocene compound (e.g., zirconocene) and an organoaluminum oxy compound (e.g., aluminoxane) as described in JP-A-61-221207, JP-B-7-121969, Japanese Patent No. 2796376, and Japanese Patent No. 4367687 may be used, and the method using a metallocene catalyst is more preferred because it can reduce the chlorine content of the resulting copolymer and the 2,1-insertion amount of propylene.

[0034] In the process using a vanadium catalyst, a larger amount of a chlorine compound is used as a co-catalyst compared to the process using a metallocene catalyst, so there is a possibility that a small amount of chlorine will remain in the obtained component (A).

[0035] On the other hand, in the method using a metallocene catalyst, since substantially no chlorine remains, there is no need to consider the possibility that the aqueous dispersion promotes corrosion of metal parts such as storage containers. The chlorine content in the copolymer is preferably 100wtppm or less, more preferably 50wtppm or less, even more preferably 20wtppm or less, and particularly preferably 5wtppm or less. The chlorine content can be quantified by various known methods. The specific measurement method in the present invention is as described in the examples.

[0036] In addition, the reduction in the amount of 2,1-insertion of propylene in component (A) makes it possible to further reduce the number of ethylene chains in the copolymer molecule, and since the intramolecular crystallinity of ethylene can be suppressed, such a copolymer has excellent dispersibility in water. The amount of 2,1-insertion of propylene can be reduced according to the method described in JP-A-7-145212. 13It is determined by C-NMR measurement and analysis, and is preferably less than 1%, more preferably 0 to 0.5%, and further preferably 0 to 0.1%. It is particularly preferable that no peak is observed in the range of 15.0 to 17.5 ppm.

[0037] In particular, by using the following method, it is possible to obtain a component (A) having a good balance of performance in terms of molecular weight control, molecular weight distribution, amorphousness, and B value. Component (A) can be produced by copolymerizing ethylene and an α-olefin in the presence of an olefin polymerization catalyst containing a bridged metallocene compound (a) represented by the following general formula [I], and at least one compound (b) selected from an organometallic compound (b-1), an organoaluminum oxy compound (b-2), and a compound (b-3) that reacts with the bridged metallocene compound (a) to form an ion pair.

[0038] [ka] <Bridged metallocene compound (a)> The bridged metallocene compound (a) is represented by the above formula [I].

[0039] Y, M, and R in formula [I] 1 ~R 14 , Q, n and j are explained below. (Y, M, R 1 ~R 14 , Q, n and j) Y is a Group 14 atom, examples of which include a carbon atom, a silicon atom, a germanium atom and a tin atom, and is preferably a carbon atom or a silicon atom, and more preferably a carbon atom.

[0040] M is a titanium atom, a zirconium atom or a hafnium atom, and is preferably a zirconium atom. R 1 ~R 12are atoms or substituents selected from a hydrogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing group, a nitrogen-containing group, an oxygen-containing group, a halogen atom, and a halogen-containing group, and may be the same or different. 1 From R 12 Adjacent substituents up to may be bonded to each other to form a ring, or may not be bonded to each other.

[0041] Examples of the hydrocarbon group having 1 to 20 carbon atoms include an alkyl group having 1 to 20 carbon atoms, a cyclic saturated hydrocarbon group having 3 to 20 carbon atoms, a linear unsaturated hydrocarbon group having 2 to 20 carbon atoms, and a cyclic unsaturated hydrocarbon group having 3 to 20 carbon atoms.

[0042] Examples of the alkyl group having 1 to 20 carbon atoms include linear saturated hydrocarbon groups such as methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decanyl, and branched saturated hydrocarbon groups such as isopropyl, isobutyl, s-butyl, t-butyl, t-amyl, neopentyl, 3-methylpentyl, 1,1-diethylpropyl, 1,1-dimethylbutyl, 1-methyl-1-propylbutyl, 1,1- J Examples include a propylbutyl group, a 1,1-dimethyl-2-methylpropyl group, a 1-methyl-1-isopropyl-2-methylpropyl group, a cyclopropylmethyl group, etc. The number of carbon atoms in the alkyl group is preferably 1 to 6.

[0043] Examples of the cyclic saturated hydrocarbon group having 3 to 20 carbon atoms include unsubstituted cyclic saturated hydrocarbon groups such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, and a norbornyl group. DExamples of such unsubstituted cyclic saturated hydrocarbon groups include a 3-methylcyclopentyl group, a 3-methylcyclohexyl group, a 4-methylcyclohexyl group, a 4-cyclohexylcyclohexyl group, and a 4-phenylcyclohexyl group, which are groups in which one or more hydrogen atoms contained in the unsubstituted cyclic saturated hydrocarbon group are replaced by a hydrocarbon group having 1 to 17 carbon atoms. The number of carbon atoms in the cyclic saturated hydrocarbon group is preferably 5 to 11.

[0044] Examples of the linear unsaturated hydrocarbon group having 2 to 20 carbon atoms include alkenyl groups such as ethenyl group (vinyl group), 1-propenyl group, 2-propenyl group (allyl group), 1-methylethenyl group (isopropenyl group), etc., and alkynyl groups such as ethynyl group, 1-propynyl group, 2-propynyl group (propargyl group), etc. The number of carbon atoms in the linear unsaturated hydrocarbon group is preferably 2 to 4.

[0045] Examples of the cyclic unsaturated hydrocarbon group having 3 to 20 carbon atoms include unsubstituted cyclic unsaturated hydrocarbon groups such as cyclopentadienyl group, norbornene group, and the like. N Examples of such groups include 3-methylphenyl (m-tolyl), 4-methylphenyl (p-tolyl), 4-ethylphenyl, 4-t-butylphenyl, 4-cyclohexylphenyl, biphenylyl, 3,4-dimethylphenyl, 3,5-dimethylphenyl, and 2,4,6-trimethylphenyl (mesityl), which are groups in which one or more hydrogen atoms contained in an unsubstituted cyclic unsaturated hydrocarbon group are replaced with a hydrocarbon group having 1 to 15 carbon atoms, such as a nyl group, a phenyl group, a naphthyl group, an indenyl group, an azulenyl group, a phenanthryl group, and an anthracenyl group, and groups in which one or more hydrogen atoms contained in a linear saturated hydrocarbon group or a branched saturated hydrocarbon group are replaced with an unsubstituted or substituted cyclic unsaturated hydrocarbon group having 3 to 19 carbon atoms, such as a benzyl group or a cumyl group. The number of carbon atoms in the cyclic unsaturated hydrocarbon group is preferably 6 to 10.

[0046] Examples of the silicon-containing group include alkylsilyl groups such as trimethylsilyl group, triethylsilyl group, t-butyldimethylsilyl group, and triisopropylsilyl group, which are groups in which at least one carbon atom in a hydrocarbon group having 1 to 20 carbon atoms is replaced with a silicon atom, arylsilyl groups such as dimethylphenylsilyl group, methyldiphenylsilyl group, and t-butyldiphenylsilyl group, pentamethyldisilanyl group, and trimethylsilylmethyl group, etc. The number of carbon atoms in the alkylsilyl group is preferably 1 to 10, and the number of carbon atoms in the arylsilyl group is preferably 6 to 18.

[0047] Examples of the nitrogen-containing group include an amino group, a group in which at least one =CH- structural unit in the above-mentioned hydrocarbon group having 1 to 20 carbon atoms or silicon-containing group is replaced with a nitrogen atom, a group in which at least one -CH2- structural unit is replaced with a nitrogen atom to which a hydrocarbon group having 1 to 20 carbon atoms is bonded, a group in which at least one -CH3 structural unit is replaced with a nitrogen atom to which a hydrocarbon group having 1 to 20 carbon atoms is bonded, or a group in which at least one -CH3 structural unit is replaced with a nitrile group, such as a dimethylamino group, a diethylamino group, an N-morpholinyl group, a dimethylaminomethyl group, a cyano group, a pyrrolidinyl group, a piperidinyl group, or a pyridinyl group. oh and nitro groups. As the nitrogen-containing group, a dimethylamino group and an N-morpholinyl group are preferred.

[0048] Examples of the oxygen-containing group include a hydroxyl group, a group in which at least one -CH2- structural unit in the above-mentioned hydrocarbon group having 1 to 20 carbon atoms, silicon-containing group, or nitrogen-containing group is replaced with an oxygen atom or a carbonyl group, or a group in which at least one -CH3 structural unit is replaced with an oxygen atom bonded to a hydrocarbon group having 1 to 20 carbon atoms, such as a methoxy group, ethoxy group, t-butoxy group, phenoxy group, trimethylsiloxy group, methoxyethoxy group, hydroxymethyl group, methoxymethyl group, ethoxymethyl group, t-butoxymethyl group, 1-hydroxymethyl group, 1-hydroxyethyl ... Examples of the oxygen-containing group include a methoxyethyl group, a 1-methoxyethyl group, a 1-ethoxyethyl group, a 2-hydroxyethyl group, a 2-methoxyethyl group, a 2-ethoxyethyl group, an n-2-oxabutylene group, an n-2-oxapentylene group, an n-3-oxapentylene group, an aldehyde group, an acetyl group, a propionyl group, a benzoyl group, a trimethylsilylcarbonyl group, a carbamoyl group, a methylaminocarbonyl group, a carboxy group, a methoxycarbonyl group, a carboxymethyl group, an ethoxycarboxymethyl group, a carbamoylmethyl group, a furanyl group, and a pyranyl group. As the oxygen-containing group, a methoxy group is preferable.

[0049] Examples of halogen atoms include Group 17 elements such as fluorine, chlorine, bromine, and iodine. Examples of the halogen-containing group include a trifluoromethyl group, a tribromomethyl group, a pentafluoroethyl group, a pentafluorophenyl group, and the like, which are groups in which at least one hydrogen atom in the above-mentioned hydrocarbon group having 1 to 20 carbon atoms, silicon-containing group, nitrogen-containing group, or oxygen-containing group is substituted with a halogen atom.

[0050] R 1 From R 12 Adjacent substituents up to R are bonded to each other to form an alkylene group having 1 to 20 carbon atoms, an arylene group having 6 to 20 carbon atoms, etc., 1 From R 12 may form a ring together with the ring carbon to which it is attached.

[0051] Examples of the alkylene group having 1 to 20 carbon atoms include a methylene group, an ethylene group, a dimethylmethylene group (an isopropylidene group), an ethylmethylene group, a methylethylene group, an n-propylene group, etc. The number of carbon atoms in the alkylene group is preferably 1 to 6.

[0052] Examples of the arylene group having 6 to 20 carbon atoms include an o-phenylene group, an m-phenylene group, a p-phenylene group, a 4,4'-biphenylylene group, etc. The number of carbon atoms in the arylene group is preferably 6 to 12.

[0053] Q may be the same or different and selected in combination from a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, an anionic ligand, and a neutral ligand capable of coordinating with a lone electron pair. Details of the halogen atom and the hydrocarbon group having 1 to 20 carbon atoms are as described above. When Q is a halogen atom, it is preferably a chlorine atom. When Q is a hydrocarbon group having 1 to 20 carbon atoms, the hydrocarbon group preferably has 1 to 7 carbon atoms.

[0054] Examples of the anionic ligand include alkoxy groups such as methoxy, t-butoxy, and phenoxy groups; carboxylate groups such as acetate and benzoate; and sulfonate groups such as mesylate and tosylate.

[0055] Examples of neutral ligands capable of coordinating with lone electron pairs include organic phosphorus compounds such as trimethylphosphine, triethylphosphine, triphenylphosphine, and diphenylmethylphosphine, and ether compounds such as tetrahydrofuran, diethyl ether, dioxane, and 1,2-dimethoxyethane.

[0056] j is an integer of 1 to 4, and is preferably 2. n is an integer of 1 to 4, preferably 1 or 2, and more preferably 1. R 13 and R 14are atoms or substituents selected from hydrogen atoms, hydrocarbon groups having 1 to 20 carbon atoms (excluding the following aryl groups and substituted aryl groups), aryl groups, substituted aryl groups, silicon-containing groups, nitrogen-containing groups, oxygen-containing groups, halogen atoms and halogen-containing groups, and may be the same or different. 13 and R 14 may be bonded to each other to form a ring, or may not be bonded to each other.

[0057] Details of the hydrocarbon group having 1 to 20 carbon atoms, the silicon-containing group, the nitrogen-containing group, the oxygen-containing group, the halogen atom and the halogen-containing group are as described above. Examples of the aryl group include, but are not limited to, the above-mentioned examples of the cyclic unsaturated hydrocarbon group having 3 to 20 carbon atoms, and are exemplified by substituents derived from aromatic compounds, such as phenyl, 1-naphthyl, 2-naphthyl, anthracenyl, phenanthrenyl, tetracenyl, chrysenyl, pyrenyl, indenyl, azulenyl, pyrrolyl, pyridyl, furanyl, and thiophenyl groups. The aryl group is preferably a phenyl group or a 2-naphthyl group.

[0058] Examples of the aromatic compounds include aromatic hydrocarbons and heterocyclic aromatic compounds such as benzene, naphthalene, anthracene, phenanthrene, tetracene, chrysene, pyrene, indene, azulene, pyrrole, pyridine, furan, and thiophene.

[0059] The substituted aryl group partially overlaps with the examples of the cyclic unsaturated hydrocarbon group having 3 to 20 carbon atoms described above, but examples thereof include groups in which one or more hydrogen atoms of the aryl group are substituted with at least one substituent selected from a hydrocarbon group having 1 to 20 carbon atoms (excluding aryl groups), an aryl group, a silicon-containing group, a nitrogen-containing group, an oxygen-containing group, a halogen atom, and a halogen-containing group. Specific examples thereof include a 3-methylphenyl group (m-tolyl group), a 4-methylphenyl group (p-tolyl group), a 3-ethylphenyl group, a 4-ethylphenyl group, a 3,4-dimethylphenyl group, a 3,5-dimethylphenyl group, a biphenylyl group, a 4-(trimethylsilyl)phenyl group, a phenylyl ... Examples of the aryl group include a 4-aminophenyl group, a 4-(dimethylamino)phenyl group, a 4-(diethylamino)phenyl group, a 4-morpholinylphenyl group, a 4-methoxyphenyl group, a 4-ethoxyphenyl group, a 4-phenoxyphenyl group, a 3,4-dimethoxyphenyl group, a 3,5-dimethoxyphenyl group, a 3-methyl-4-methoxyphenyl group, a 3,5-dimethyl-4-methoxyphenyl group, a 3-(trifluoromethyl)phenyl group, a 4-(trifluoromethyl)phenyl group, a 3-chlorophenyl group, a 4-chlorophenyl group, a 3-fluorophenyl group, a 4-fluorophenyl group, a 5-methylnaphthyl group, and a 2-(6-methyl)pyridyl group.

[0060] R 13 and R 14 are bonded to each other to form an alkylene group having 1 to 20 carbon atoms, an arylene group having 6 to 20 carbon atoms, etc., and R 13 and R 14 may form a ring together with Y to which it is bonded. Specific examples of the alkylene group and the arylene group are as described above.

[0061] In the bridged metallocene compound (a) represented by the above formula [I], n is preferably 1. Such a bridged metallocene compound is hereinafter also referred to as "bridged metallocene compound (a-1)".

[0062] The bridged metallocene compound (a-1) has a simplified production process and reduced production costs compared to the compound in the above formula [I] where n is an integer of 2 to 4. Thus, the use of this bridged metallocene compound (a-1) offers the advantage of reducing the production costs of the ethylene-α-olefin copolymer (A).

[0063] In the bridged metallocene compound (a-1), R 1 , R 2 , R 3 and R 4 are preferably all hydrogen atoms. Such a bridged metallocene compound is hereinafter also referred to as "bridged metallocene compound (a-2)".

[0064] The bridged metallocene compound (a-2) is represented by R 1 , R 2 , R 3 and R 4 In comparison with a compound in which one or more of the above are substituted with a substituent other than a hydrogen atom, the production process is simplified and the production cost is reduced, and thus the use of this bridged metallocene compound (a-2) has the advantage of reducing the production cost of the ethylene-α-olefin copolymer (A). In addition, although it is generally known that high-temperature polymerization reduces the randomness of the ethylene-α-olefin copolymer (A), when ethylene and an α-olefin are copolymerized in the presence of an olefin polymerization catalyst containing the bridged metallocene compound (a-2), the ethylene-α-olefin copolymer (A) obtained has the advantage of being highly random, even in high-temperature polymerization.

[0065] In the bridged metallocene compound (a-2), R 13 and R 14 It is preferable that either one of R is an aryl group or a substituted aryl group. Such a bridged metallocene compound is hereinafter also referred to as "bridged metallocene compound (a-3)". The bridged metallocene compound (a-3) is 13 and R 14The resulting ethylene-α-olefin copolymers are more stable than those in which all the substituents are other than aryl and substituted aryl groups. ( A) Medium The advantage of this is that the amount of double bonds is small.

[0066] In the bridged metallocene compound (a-3), R 13 and R 14 It is more preferable that one of R is an aryl group or a substituted aryl group, and the other is an alkyl group having 1 to 20 carbon atoms. 13 and R 14 It is particularly preferred that one of R is an aryl group or a substituted aryl group, and the other is a methyl group. Such a bridged metallocene compound is hereinafter also referred to as "bridged metallocene compound (a-4)". The bridged metallocene compound (a-4) is 13 and R 14 In comparison with the case where all of the substituents are aryl groups or substituted aryl groups, the bridged metallocene compound has a better balance between the amount of double bonds in the resulting ethylene-α-olefin copolymer (A) and the polymerization activity, and the use of this bridged metallocene compound offers the advantage of reducing the production costs of the ethylene-α-olefin copolymer (A).

[0067] When polymerization is carried out under certain conditions of total pressure and temperature in a polymerization reactor, an increase in hydrogen partial pressure due to hydrogen introduction causes a decrease in the partial pressure of the olefin, which is the polymerization monomer, and there is a problem that the polymerization rate decreases, especially in the region where the hydrogen partial pressure is high. Since the internal total pressure allowed by the design of a polymerization reactor is limited, if excessive hydrogen introduction is required, especially when producing a low molecular weight olefin polymer, the olefin partial pressure decreases significantly, and the polymerization activity may decrease. However, when the ethylene-α-olefin copolymer (A) is produced using the bridged metallocene compound (a-4), the amount of hydrogen introduced into the polymerization reactor is reduced compared to the case of using the bridged metallocene compound (a-3), and the polymerization activity is improved, resulting in a reduction in the production cost of the ethylene-α-olefin copolymer (A).

[0068] In the bridged metallocene compound (a-4), R 6 and R 11 is preferably an alkyl group having 1 to 20 carbon atoms, or an alkylene group having 1 to 20 carbon atoms formed by bonding with adjacent substituents. Such a bridged metallocene compound is hereinafter also referred to as "bridged metallocene compound (a-5)". The bridged metallocene compound (a-5) is 6 and R 11 In comparison with a compound in which the bridged metallocene compound (a-5) is substituted with a substituent other than an alkyl group having 1 to 20 carbon atoms and an alkylene group having 1 to 20 carbon atoms, the production process is simplified and the production cost is reduced, and thus the use of this bridged metallocene compound (a-5) has the advantage of reducing the production cost of the ethylene-α-olefin copolymer (A).

[0069] In the bridged metallocene compounds (a), (a-1), (a-2), (a-3), (a-4) and (a-5), M is more preferably a zirconium atom. When ethylene and an α-olefin are copolymerized in the presence of an olefin polymerization catalyst containing the above bridged metallocene compound in which M is a zirconium atom, the polymerization activity is higher than when M is a titanium atom or a hafnium atom, and the production cost of the ethylene-α-olefin copolymer (A) can be advantageously reduced.

[0070] Examples of such bridged metallocene compounds (a) include [dimethylmethylene(η5-cyclopentadienyl)(η5-fluorenyl)]zirconium dichloride, [dimethylmethylene(η5-cyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [dimethylmethylene(η5-cyclopentadienyl)(η5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [dimethylmethylene(η5-cyclopentadienyl)(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [dimethylmethylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [cyclohexylidene(η5-cyclopentadienyl)(η5-fluorenyl)]zirconium dichloride, [cyclohexylidene(η5-cyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [cyclohexylidene(η5-cyclopentadienyl)(η5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [cyclohexylidene(η5-cyclopentadienyl)(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [cyclohexylidene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [diphenylmethylene(η5-cyclopentadienyl)(η5-fluorenyl)]zirconium dichloride, [diphenylmethylene(η5-cyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [ diphenylmethylene(η5-2-methyl-4-t-butylcyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [diphenylmethylene(η5-cyclopentadienyl)(η5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [diphenylmethylene(η5-cyclopentadienyl)(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [ diphenylmethylene{η5-(2-methyl-4-i-propylcyclopentadienyl)}(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [diphenylmethylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [methylphenylmethylene(η5-cyclopentadienyl)(η5-fluorenyl)]zirconium dichloride, [methylphenylmethylene(η5-cyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [methylphenylmethylene(η5-cyclopentadienyl)(η5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [methylphenylmethylene(η5-cyclopentadienyl)(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [methylphenylmethylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η5-cyclopentadienyl)(η5-fluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η5-cyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η5-cyclopentadienyl)(η5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η5-cyclopentadienyl)(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [diphenylsilylene(η5-cyclopentadienyl)(η5-fluorenyl)]zirconium dichloride, [diphenylsilylene(η5-cyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [diphenylsilylene(η5-cyclopentadienyl)(η5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [diphenylsilylene(η5-cyclopentadienyl)(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [diphenylsilylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η5-cyclopentadienyl)(η5-fluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η5-cyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η5-cyclopentadienyl)(η5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η5-cyclopentadienyl)(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η5-cyclopentadienyl)(η5-fluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η5-cyclopentadienyl)(η5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η5-cyclopentadienyl)(η5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η5-cyclopentadienyl)(η5-octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η5-cyclopentadienyl)(η5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Ethylene (η5-cyclopentadienyl) (η5-fluorenyl)] zirconium dichloride, [ethylene (η5-cyclopentadienyl) (η5-2,7-di-t-butylfluorenyl)] zirconium dichloride, [ethylene (η5-cyclopentadienyl) (η5-3,6-di-t-butylfluorenyl)] zirconium dichloride, [ethylene (η5-cyclopentadienyl) (η5-octamethyloctahydrodibenzofluorenyl)] zirconium dichloride, [ethylene (η5-cyclopentadienyl) (η5-tetramethyloctahydrodibenzofluorenyl)] zirconium dichloride, etc.

[0071] Examples include compounds in which the zirconium atoms of these compounds are replaced with hafnium atoms, compounds in which chloro ligands are replaced with methyl groups, etc., but the bridged metallocene compound (a) is not limited to these examples. Incidentally, η5-tetramethyloctahydrodibenzofluorenyl, which is a constituent of the exemplified bridged metallocene compound (a), represents a 4,4,7,7-tetramethyl-(5a,5b,11a,12,12a-η5)-1,2,3,4,7,8,9,10-octahydrodibenzo[b,H]fluorenyl group, and η5-octamethyloctahydrodibenzofluorenyl represents a 1,1,4,4,7,7,10,10-octamethyl-(5a,5b,11a,12,12a-η5)-1,2,3,4,7,8,9,10-octahydrodibenzo[b,H]fluorenyl group, respectively.

[0072] <Compound (b)> The polymerization catalyst preferably used in the present invention contains at least one compound (b) selected from the group consisting of a bridged metallocene compound (a), an organometallic compound (b-1), an organoaluminum oxy compound (b-2), and a compound (b-3) that reacts with the bridged metallocene compound (a) to form an ion pair.

[0073] Specific examples of the organometallic compound (b-1) include organometallic compounds of Groups 1, 2, 12, and 13 of the periodic table as follows. (b-1a) General formula R a mAl(OR b )nHpXq (In the formula, R a and R b may be the same or different from each other and represent a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms. X represents a halogen atom. m is a number where 0 < m ≤ 3, n is a number where 0 ≤ n < 3, p is a number where 0 ≤ p < 3, q is a number where 0 ≤ q < 3, and m + n + p + q = 3.) Organoaluminum compounds represented by the formula.

[0074] Examples of such compounds include tri-n-alkylaluminum such as trimethylaluminum, triethylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, and tri-n-octylaluminum; triisopropylaluminum; triisobutylaluminum; and triisopropylaluminum. - tribranched alkylaluminums such as sec-butylaluminum, tri-t-butylaluminum, tri-2-methylbutylaluminum, tri-3-methylhexylaluminum, and tri-2-ethylhexylaluminum; tricycloalkylaluminums such as tricyclohexylaluminum and tricyclooctylaluminum; triarylaluminums such as triphenylaluminum and tri(4-methylphenyl)aluminum; dialkylaluminum hydrides such as diisopropylaluminum hydride and diisobutylaluminum hydride; 10 )z (wherein x, y, and z are positive numbers, and z≦2x); alkylaluminum alkoxides such as isobutylaluminum methoxide and isobutylaluminum ethoxide; dialkylaluminum alkoxides such as dimethylaluminum methoxide, diethylaluminum ethoxide, and dibutylaluminum butoxide; alkylaluminum sesquialkoxides such as ethylaluminum sesquiethoxide and butylaluminum sesquibutoxide; a 2.5 Al(OR b ) 0.5Examples of the alkylaluminum include partially alkoxylated alkylaluminums having an average composition represented by the formula: alkylaluminum aryloxides such as diethylaluminum phenoxide and diethylaluminum (2,6-di-t-butyl-4-methylphenoxide); dialkylaluminum halides such as dimethylaluminum chloride, diethylaluminum chloride, dibutylaluminum chloride, diethylaluminum bromide and diisobutylaluminum chloride; alkylaluminum sesquihalides such as ethylaluminum sesquichloride, butylaluminum sesquichloride and ethylaluminum sesquibromide; partially halogenated alkylaluminums such as alkylaluminum dihalides such as ethylaluminum dichloride; dialkylaluminum hydrides such as diethylaluminum hydride and dibutylaluminum hydride; alkylaluminum dihydrides such as ethylaluminum dihydride and propylaluminum dihydride; and other partially hydrogenated alkylaluminums; partially alkoxylated and halogenated alkylaluminums such as ethylaluminum ethoxy chloride, butylaluminum butoxy chloride and ethylaluminum ethoxy bromide.

[0075] In addition, the above general formula R a mAl(OR b Compounds similar to the compound represented by the formula (III)nHpXq can also be used, such as organoaluminum compounds in which two or more aluminum compounds are bonded via nitrogen atoms. Specific examples of such compounds include (C2H5)2AlN(C2H5)Al(C2H5)2.

[0076] (b-1b) General formula M 2 AlR a 4 (in the formula, M 2 indicates Li, Na or K, and R a represents a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms.

[0077] Such compounds include LiAl(C2H5)4, LiAl(C7H 15 ) 4 can be given as an example. (b-1c) General formula R a R b M 3 (In the formula, R a and R b may be the same or different and each represents a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms; M 3 is Mg, Zn or Cd.) Dialkyl compounds of metals in Group 2 or 12 of the Periodic Table.

[0078] As the organoaluminum oxy compound (b-2), a conventionally known aluminoxane can be used as it is.Specific examples include compounds represented by the following general formula [II] and compounds represented by the following general formula [III].

[0079] [ka] In the formulas [II] and [III], R represents a hydrocarbon group having 1 to 10 carbon atoms, and n represents an integer of 2 or more.

[0080] In particular, methylaluminoxanes in which R is a methyl group and n is at least 3, preferably at least 10, are used. There is no problem if these aluminoxanes contain a small amount of an organoaluminum compound.

[0081] When copolymerization of ethylene and α-olefin is carried out at high temperature, benzene-insoluble organoaluminum oxy compounds as exemplified in JP-A-2-78687 can also be used. In addition, organoaluminum oxy compounds as described in JP-A-2-167305, aluminoxanes having two or more alkyl groups as described in JP-A-2-24701 and JP-A-3-103407, etc. can also be suitably used. The "benzene-insoluble organoaluminum oxy compounds" that may be used in the present invention are compounds that are insoluble or poorly soluble in benzene, and that have an Al component that dissolves in benzene at 60°C in terms of Al atoms of usually 10% or less, preferably 5% or less, and particularly preferably 2% or less.

[0082] Further, the organoaluminum oxy compound (b-2) may also include modified methylaluminoxanes as represented by the following general formula [IV].

[0083] [ka] In formula [IV], Me represents a methyl group, R represents a hydrocarbon group having 2 to 10 carbon atoms, and m and n each independently represent an integer of 2 or more.

[0084] This modified methylaluminoxane is prepared using trimethylaluminum and an alkylaluminum other than trimethylaluminum. Such compounds are generally called MMAO. Such MMAO can be prepared by the methods described in U.S. Patent No. 4,960,878 and U.S. Patent No. 5,041,584. Tosoh Finechem and other companies also sell MMAO and TMAO, which are prepared using trimethylaluminum and triisobutylaluminum, where R is an isobutyl group. Such MMAO is an aluminoxane with improved solubility in various solvents and storage stability. Specifically, unlike the compounds represented by the above formula [II] and the above formula [III], which are insoluble or poorly soluble in benzene, MMAO dissolves in aliphatic and alicyclic hydrocarbons.

[0085] Further, the organoaluminum oxy compound (b-2) may also include an organoaluminum oxy compound containing boron represented by the following general formula [V].

[0086] [ka] In formula [V], R c R represents a hydrocarbon group having 1 to 10 carbon atoms. d may be the same or different and represent a hydrogen atom, a halogen atom, or a hydrocarbon group having 1 to 10 carbon atoms.

[0087] Examples of the compound (b-3) that reacts with the bridged metallocene compound (a) to form an ion pair (hereinafter sometimes abbreviated as "ionized ionic compound" or simply "ionic compound") include Lewis acids, ionic compounds, borane compounds, and carborane compounds described in JP-A-1-501950, JP-A-1-502036, JP-A-3-179005, JP-A-3-179006, JP-A-3-207703, JP-A-3-207704, and U.S. Patent No. 5,321,106. Further examples include heteropoly compounds and isopoly compounds.

[0088] The ionizing ionic compound preferably used in the present invention is a boron compound represented by the following general formula [VI].

[0089] [ka] In formula [VI], R e+ As for H + , carbenium cation, oxonium cation, ammonium cation, phosphonium cation, cycloheptyltrienyl cation, ferrocenium cation having a transition metal, etc. f ~R imay be the same or different and are substituents selected from a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing group, a nitrogen-containing group, an oxygen-containing group, a halogen atom and a halogen-containing group, and are preferably substituted aryl groups.

[0090] Specific examples of the carbenium cation include tri-substituted carbenium cations such as triphenylcarbenium cation, tris(4-methylphenyl)carbenium cation, and tris(3,5-dimethylphenyl)carbenium cation.

[0091] Specific examples of the ammonium cation include trialkyl-substituted ammonium cations such as trimethylammonium cation, triethylammonium cation, tri(n-propyl)ammonium cation, triisopropylammonium cation, tri(n-butyl)ammonium cation, and triisobutylammonium cation; N,N-dialkylanilinium cations such as N,N-dimethylanilinium cation, N,N-diethylanilinium cation, and N,N-2,4,6-pentamethylanilinium cation; and dialkylammonium cations such as diisopropylammonium cation and dicyclohexylammonium cation.

[0092] Specific examples of the phosphonium cation include triarylphosphonium cations such as triphenylphosphonium cation, tris(4-methylphenyl)phosphonium cation, and tris(3,5-dimethylphenyl)phosphonium cation.

[0093] R e+ Of the above specific examples, preferred are carbenium cations and ammonium cations, with triphenylcarbenium cation, N,N-dimethylanilinium cation and N,N-diethylanilinium cation being particularly preferred.

[0094] Among the ionized ionic compounds preferably used in the present invention, examples of compounds containing a carbenium cation include triphenylcarbenium tetraphenylborate, triphenylcarbenium tetrakis(pentafluorophenyl)borate, triphenylcarbenium tetrakis{3,5-di-(trifluoromethyl)phenyl}borate, tris(4-methylphenyl)carbenium tetrakis(pentafluorophenyl)borate, and tris(3,5-dimethylphenyl)carbenium tetrakis(pentafluorophenyl)borate.

[0095] Among the ionizing ionic compounds preferably used in the present invention, compounds containing a trialkyl-substituted ammonium cation include triethylammonium tetraphenylborate, tripropylammonium tetraphenylborate, tri(n-butyl)ammonium tetraphenylborate, trimethylammonium tetrakis(4-methylphenyl)borate, trimethylammonium tetrakis(2-methylphenyl)borate, tri(n-butyl)ammonium tetrakis(pentafluorophenyl)borate, triethylammonium tetrakis(pentafluorophenyl)borate, tripropyl ... tri(pentafluorophenyl)borate, tripropylammonium tetrakis(2,4-dimethylphenyl)borate, tri(n-butyl)ammonium tetrakis(3,5-dimethylphenyl)borate, tri(n-butyl)ammonium tetrakis{4-(trifluoromethyl)phenyl}borate, tri(n-butyl)ammonium tetrakis{3,5-di(trifluoromethyl)phenyl}borate, tri(n-butyl)ammonium tetrakis(2-methylphenyl)borate, dioctadecylmethylammonium tetraphenylborate, dioctadecylmethylammonium tetrakis(4-methylphenyl)borate, JExamples of the tetrakis include octadecylmethylammonium tetrakis(pentafluorophenyl)borate, dioctadecylmethylammonium tetrakis(2,4-dimethylphenyl)borate, dioctadecylmethylammonium tetrakis(3,5-dimethylphenyl)borate, dioctadecylmethylammonium tetrakis{4-(trifluoromethyl)phenyl}borate, dioctadecylmethylammonium tetrakis{3,5-di(trifluoromethyl)phenyl}borate, and dioctadecylmethylammonium.

[0096] Among the ionizing ionic compounds preferably used in the present invention, examples of compounds containing an N,N-dialkylanilinium cation include N,N-dimethylanilinium tetraphenylborate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis{3,5-di(trifluoromethyl)phenyl}borate, N,N-diethylanilinium tetraphenylborate, N,N-diethylanilinium tetrakis(pentafluorophenyl)borate, N,N-diethylanilinium tetrakis{3,5-di(trifluoromethyl)phenyl}borate, N,N-2,4,6-pentamethylanilinium tetraphenylborate, and N,N-2,4,6-pentamethylanilinium tetrakis(pentafluorophenyl)borate.

[0097] Among the ionizing ionic compounds preferably used in the present invention, examples of compounds containing a dialkylammonium cation include di-n-propylammonium tetrakis(pentafluorophenyl)borate and dicyclohexylammonium tetraphenylborate.

[0098] In addition, the ionic compounds exemplified in JP-A-2004-51676 can also be used without any restrictions. The above ionic compound (b-3) may be used alone or in combination of two or more. hand Good too.

[0099] As the organometallic compound (b-1), trimethylaluminum, triethylaluminum and triisobutylaluminum are preferred, which are commercially available and therefore easily available, and among these, triisobutylaluminum, which is easy to handle, is particularly preferred.

[0100] As the organoaluminum oxy compound (b-2), methylaluminoxane, which is commercially available and therefore easily available, and MMAO prepared using trimethylaluminum and triisobutylaluminum are preferred. Among these, MMAO, which has improved solubility in various solvents and storage stability, is particularly preferred.

[0101] As the ionic compound (b-3), triphenylcarbenium tetrakis(pentafluorophenyl)borate and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate are preferred because they are easily available as commercial products and contribute greatly to improving the polymerization activity.

[0102] As the compound (b), a combination of triisobutylaluminum and triphenylcarbenium tetrakis(pentafluorophenyl)borate, and a combination of triisobutylaluminum and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate are particularly preferred because they greatly improve the polymerization activity.

[0103] <Carrier (c)> In the present invention, a support (c) may be used as a constituent component of the olefin polymerization catalyst, if necessary.

[0104] The carrier (c) which may be used in the present invention is an inorganic or organic compound, which is a granular or particulate solid. Among these, the inorganic compound is preferably a porous oxide, an inorganic chloride, a clay, a clay mineral, or an ion-exchangeable layered compound.

[0105] As the porous oxide, specifically, SiO2, Al2O3, MgO, ZrO, TiO2, B2O3, CaO, ZnO, BaO, ThO2, etc., or a composite or mixture containing these, such as natural or synthetic zeolite, SiO2-MgO, SiO2-Al2O3, SiO2-TiO2, SiO2-V2O5, SiO2-Cr2O3, SiO2-TiO2-MgO, etc. can be used. Among these, those containing SiO2 and / or Al2O3 as the main component are preferred. Although the properties of such porous oxides vary depending on the type and manufacturing method, the carrier preferably used in the present invention has a particle size of 0.5 to 300 μm, preferably 1.0 to 200 μm, and a specific surface area of ​​50 to 1000 m. 2 / g, preferably 100 to 700m 2 / g and the pore volume is 0.3-3.0 cm 3 The carrier is calcined at 100 to 1000° C., preferably 150 to 700° C., as required, before use.

[0106] Examples of inorganic chlorides that can be used include MgCl2, MgBr2, MnCl2, and MnBr2. The inorganic chlorides can be used as they are, or can be used after being pulverized by a ball mill or a vibration mill. In addition, the inorganic chlorides can be dissolved in a solvent such as alcohol, and then precipitated into fine particles using a precipitating agent.

[0107] Clay is usually composed of clay minerals as the main component. In addition, an ion-exchangeable layered compound is a compound having a crystal structure in which the constituent faces are stacked in parallel with each other with weak bonding force due to ionic bonds, etc., and the ions contained therein are exchangeable. Most clay minerals are ion-exchangeable layered compounds. In addition, these clays, clay minerals, and ion-exchangeable layered compounds are not limited to natural products, and artificial synthetic products can also be used. In addition, examples of clays, clay minerals, and ion-exchangeable layered compounds include clays, clay minerals, and ionic crystalline compounds having layered crystal structures such as hexagonal close packing type, antimony type, CdCl2 type, and CdI2 type. Examples of such clays and clay minerals include kaolin, bentonite, kibushi clay, gairome clay, allophane, hisingerite, pyrophyllite, ummo group, montmorillonite group, vermiculite, ryokudeite group, palygorskite, kaolinite, nacrite, dickite, and halloysite, and examples of ion-exchangeable layered compounds include α-Zr(HAsO4)2·H2O, α-Zr(HPO4)2, α-Zr(KPO4)2·3H2O, α-Ti(HPO4)2, α-Ti(HAsO4)2·H2O, α-Sn(HPO4)2·H2O, γ-Zr(HPO4)2, γ-Ti(HPO4)2, and γ-Ti(NH4PO4)2·H2O, and other crystalline acid salts of polyvalent metals. It is also preferable to subject the clay and clay minerals used in the present invention to chemical treatment. The chemical treatment may be any of surface treatments that remove impurities adhering to the surface, treatments that affect the crystal structure of the clay, etc. Specific examples of the chemical treatment include acid treatment, alkali treatment, salt treatment, and organic matter treatment.

[0108] The ion-exchangeable layered compound may be a layered compound in which the space between layers is expanded by utilizing the ion exchangeability and exchanging the exchangeable ions between layers with other large bulky ions. Such bulky ions play a role of supporting the layered structure and are usually called pillars. The introduction of another substance (guest compound) between layers of a layered compound in this way is called intercalation. Examples of guest compounds include cationic inorganic compounds such as TiCl4 and ZrCl4, metal alkoxides such as Ti(OR)4, Zr(OR)4, PO(OR)3, and B(OR)3 (R is a hydrocarbon group, etc.), [Al 13 O4(OH) 24 ] 7+ , [Zr4(OH) 14 ] 2+ , [Fe3O(OCOCH3)6] + Metal hydroxide ions such as these can be used. These compounds can be used alone or in combination of two or more. When these compounds are intercalated, polymers obtained by hydrolysis and polycondensation of metal alkoxides such as Si(OR)4, Al(OR)3, Ge(OR)4 (R is a hydrocarbon group, etc.), colloidal inorganic compounds such as SiO2, etc. can also be coexisted. Examples of pillars include oxides produced by intercalating the above metal hydroxide ions between layers and then dehydrating them with heat.

[0109] Of these, clay or clay minerals are preferred, and montmorillonite, vermiculite, pectolite, taeniolite and synthetic mica are particularly preferred. The organic compound as the carrier (c) may be a granular or fine particle solid having a particle size in the range of 0.5 to 300 μm. Specifically, it may be a (co)polymer formed mainly from an α-olefin having 2 to 14 carbon atoms, such as ethylene, propylene, 1-butene, or 4-methyl-1-pentene, or a (co)polymer formed mainly from vinylcyclohexane or styrene, or a derivative thereof. sex An example of this is the body.

[0110] High-temperature polymerization is possible by a polymerization method using an olefin polymerization catalyst capable of producing an ethylene-α-olefin copolymer (A) with high randomness. That is, by using the olefin polymerization catalyst, it is possible to suppress the decrease in randomness of the ethylene-α-olefin copolymer (A) produced during high-temperature polymerization. In solution polymerization, the viscosity of the polymerization solution containing the produced ethylene-α-olefin copolymer (A) decreases at high temperatures, so that it is possible to increase the concentration of the ethylene-α-olefin copolymer (A) in the polymerization vessel compared to low-temperature polymerization, and as a result, the productivity per polymerization vessel is improved. The copolymerization of ethylene and α-olefin in the present invention can be carried out by either a liquid phase polymerization method such as solution polymerization or suspension polymerization (slurry polymerization) or a gas phase polymerization method, but from the viewpoint of maximizing the effects of the present invention, solution polymerization is particularly preferable.

[0111] The use and order of addition of each component of the olefin polymerization catalyst may be selected arbitrarily, and at least two of the components in the catalyst may be pre-contacted. The bridged metallocene compound (a) (hereinafter also referred to as "component (a)") is usually used in an amount of 10 -9 ~10 -1 Molar, preferably 10 -8 ~10 -2 It is used in molar amounts.

[0112] The organometallic compound (b-1) (hereinafter also referred to as "component (b-1)") is used in an amount such that the molar ratio of component (b-1) to the transition metal atom (M) in component (a) [(b-1) / M] is usually 0.01 to 50,000, preferably 0.05 to 10,000.

[0113] The organoaluminum oxy compound (b-2) (hereinafter also referred to as "component (b-2)") is used in an amount such that the molar ratio [(b-2) / M] of the aluminum atom in component (b-2) to the transition metal atom (M) in component (a) is usually 10 to 5,000, preferably 20 to 2,000.

[0114] The ionic compound (b-3) (hereinafter also referred to as "component (b-3)") is used in an amount such that the molar ratio of component (b-3) to the transition metal atom (M) in component (a) [(b-3) / M] is usually 1 to 10,000, preferably 1 to 5,000.

[0115] The polymerization temperature is usually -50°C to 300°C, preferably 30°C to 250°C, more preferably 100°C to 250°C, and further preferably 130°C to 200°C. In the polymerization temperature range, as the temperature increases, the solution viscosity during polymerization decreases and the heat of polymerization is easily removed. The polymerization pressure is usually normal pressure to 10 MPa gauge pressure (MPa-G), and preferably normal pressure to 8 MPa-G.

[0116] The polymerization reaction can be carried out in any of batch, semi-continuous and continuous systems. Furthermore, the polymerization can be carried out continuously in two or more polymerization vessels with different reaction conditions. The molecular weight of the resulting copolymer can be adjusted by changing the hydrogen concentration in the polymerization system or the polymerization temperature. It can also be adjusted by the amount of compound (b) used. When hydrogen is added, the amount of hydrogen is appropriately about 0.001 to 5,000 NL per kg of the copolymer produced.

[0117] The polymerization solvent used in the liquid phase polymerization method is usually an inert hydrocarbon solvent, preferably a saturated hydrocarbon having a boiling point of 50°C to 200°C under normal pressure. Specific examples of the polymerization solvent include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene, and alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane, and particularly preferably hexane, heptane, octane, decane, and cyclohexane. The α-olefin itself, which is the object of polymerization, can also be used as the polymerization solvent. Incidentally, aromatic hydrocarbons such as benzene, toluene, and xylene, and halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane can also be used as the polymerization solvent, but from the viewpoint of reducing the burden on the environment and minimizing the impact on human health, the use of these is not preferred.

[0118] The kinetic viscosity of the ethylene-α-olefin copolymer (A) at 100°C depends on the molecular weight of the copolymer. That is, the higher the molecular weight, the higher the viscosity, and the lower the molecular weight, the lower the viscosity. Therefore, the kinetic viscosity at 100°C is adjusted by adjusting the molecular weight as described above. In addition, the molecular weight distribution (Mw / Mn) of the obtained copolymer can be adjusted by removing low molecular weight components from the obtained copolymer by a conventionally known method such as vacuum distillation. Furthermore, the obtained copolymer may be subjected to hydrogen addition (hereinafter also referred to as "hydrogenation") by a conventionally known method. If the amount of unsaturated bonds in the obtained copolymer is reduced by hydrogenation, the oxidation stability and heat resistance are improved.

[0119] [Ethylene / α-olefin copolymer acid modified thing (B)] The acid-modified ethylene / α-olefin copolymer forming the aqueous dispersion of the present invention thing (B) is an acid-modified ethylene-α-olefin copolymer (A). thing The acid denaturation thing (B) is also called "component (B)" or "acid-modified ethylene-α-olefin copolymer (B)".

[0120] The acid-modified product (B) according to the present invention is obtained by modifying the ethylene-α-olefin copolymer (A) with a compound selected from unsaturated carboxylic acids and their derivatives. death The compound is preferably an ethylene-α-olefin copolymer graft-modified with the compound.

[0121] Examples of unsaturated carboxylic acids and derivatives thereof include unsaturated carboxylic acids having 3 to 10 carbon atoms, preferably 3 to 8 carbon atoms, and derivatives of the unsaturated carboxylic acids. Examples of derivatives of unsaturated carboxylic acids include acid anhydrides, esters, amides, and imides of unsaturated carboxylic acids.

[0122] As mentioned above, component (A), which is the starting material for component (B), has a small amount of unsaturated bonds, so it is presumed that component (B) has a structure in which the graft components are randomly grafted to the main chain skeleton of component (A).

[0123] Examples of the unsaturated carboxylic acid include monobasic acids such as acrylic acid and methacrylic acid; and dibasic acids such as maleic acid, fumaric acid, itaconic acid, citraconic acid, and 5-norbornene-2,3-dicarboxylic acid.

[0124] Examples of the acid anhydrides of unsaturated carboxylic acids include acid anhydrides of dibasic acids such as maleic acid, itaconic acid, citraconic acid, and 5-norbornene-2,3-dicarboxylic acid.

[0125] Examples of the esters of unsaturated carboxylic acids include esters and half esters such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, glycidyl acrylate, monoethyl maleate, diethyl maleate, monomethyl fumarate, dimethyl fumarate, monomethyl itaconic acid, and diethyl itaconic acid.

[0126] Examples of the amide of the unsaturated carboxylic acid include acrylamide, methacrylamide, maleic acid monoamide, maleic acid diamide, maleic acid-N-monoethylamide, maleic acid-N,N-diethylamide, maleic acid-N-monobutylamide, maleic acid-N,N-dibutylamide, fumaric acid monoamide, fumaric acid diamide, fumaric acid-N-monobutylamide, and fumaric acid-N,N-dibutylamide.

[0127] Examples of the imide of the unsaturated carboxylic acid include maleimide, N-butylmaleimide, and N-phenylmaleimide. Among these, at least one selected from maleic acid and maleic anhydride is preferred because it has high polarity as a monomer and is less likely to produce by-products such as homopolymers in a modification reaction using a peroxide.

[0128] The graft component may be used alone or in combination of two or more kinds. The grafting reaction is carried out by adding the graft component to the ethylene-α-olefin copolymer (A) in the presence of a radical initiator such as di-t-butyl peroxide, for example, by the method described in JP-A-61-126120. The reaction temperature is usually 150-200°C, preferably 160-180°C, and the reaction time is usually 1-50 hours, preferably 1-10 hours. The graft component is preferably used in an amount such that the acid value of the resulting component (B) falls within the following range:

[0129] The ethylene-α-olefin copolymer according to the present invention is acid-modified thing (B) is an acid-modified ethylene-α-olefin copolymer (A) that satisfies the above (A1) to (A6). thing and satisfies the following (B1) to (B5).

[0130] (B1) The acid value is in the range of 1 to 300 mg KOH / g. The acid value is used as an index of the graft amount of the graft component. The acid value of component (B) is preferably in the range of 1 to 300 mgKOH / g, more preferably 5 to 200 mgKOH / g, and further preferably 10 to 150 mgKOH / g. If the acid value is below the above range, the polarity of the copolymer may be reduced, and the stability of the aqueous dispersion may be reduced. If the acid value is above the above range, hydrogen bonds may be formed between the graft components, which may increase the viscosity of the copolymer and result in reduced dispersibility in water.

[0131] The acid value of component (B) can be adjusted by the graft amount of the graft component to component (A). For example, in order to increase the acid value of component (B), it is preferable to increase the graft amount.

[0132] The acid value of component (B) indicates the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of the polymer, and can be measured by a method in accordance with JIS K0070. Specifically, it is as described in the Examples.

[0133] (B2) The apparent viscosity at 150°C is in the range of 1 to 1,000 cPs. The apparent viscosity (Brookfield viscosity) of component (B) at 150°C is a value measured by the method described in JIS K7117-1. The apparent viscosity of component (B) at 150°C is preferably in the range of 1 to 1,000 cPs, more preferably 5 to 800 cPs, and particularly preferably 5 to 90 cPs. When the apparent viscosity is in the above range, the composition is excellent in terms of the balance between low volatility, handleability, and dispersibility in water.

[0134] (B3) The weight average molecular weight, as calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) is in the range of 1,000 to 50,000. The weight average molecular weight (Mw) of component (B) is a value obtained by measuring by gel permeation chromatography (GPC) according to the method described later and converting it into standard polystyrene. The weight average molecular weight (Mw) of component (B) is preferably in the range of 1,000 to 50,000, more preferably 1,000 to 30,000, even more preferably 1,500 to 30,000, particularly preferably 2,000 to 7,000, and most preferably 5,000 to 6,000. If Mw is excessively below the above range, the amount of easily volatile components is high, making it easy to ignite, and the storage stability may deteriorate, or the evaporation loss in the aqueous dispersion may increase. If Mw is excessively above the above range, the viscosity of the copolymer increases, making it difficult to disperse uniformly in water.

[0135] (B4) The molecular weight distribution (Mw / Mn) measured by gel permeation chromatography (GPC) and calculated as polystyrene is 2.5 or less.

[0136] The molecular weight distribution of component (B) is measured by gel permeation chromatography (GPC) according to the method described below, and is calculated as the ratio (Mw / Mn) of the weight average molecular weight (Mw) obtained by standard polystyrene conversion to the number average molecular weight (Mn). The Mw / Mn of component (B) is preferably 2.5 or less, more preferably 2.3 or less, and even more preferably 2.0 or less. When the molecular weight distribution excessively exceeds the above range, it means that the copolymer contains a large amount of low molecular weight components and high molecular weight components. When the copolymer contains a large amount of low molecular weight components, it is likely to be flammable due to the large amount of easily volatile components, which may deteriorate the storage stability or increase the evaporation loss in the aqueous dispersion. When the copolymer contains a large amount of high molecular weight components, the viscosity of the copolymer increases, which may make it difficult to disperse uniformly in water.

[0137] (B5) The weight fraction of unreacted molecules as measured by high performance liquid chromatography (HPLC) is 59% or less. The weight fraction of unreacted molecules is within the above range. ToIn addition, the component (B) contains an unsaturated carboxylic acid or its derivative that has excellent affinity for water. thing This is preferable because it increases the proportion of molecules of component (B) and makes it easier to disperse component (B) uniformly in water.

[0138] It is preferable that the component (B) according to the present invention further satisfies the following (B6). (B6) Acid denaturation thing Of the unreacted molecules contained in (B), the weight fraction of unreacted molecules having a molecular weight higher than the weight average molecular weight of the acid-modified product (B) obtained in terms of polystyrene, as measured by gel permeation chromatography (GPC), is 20% or less.

[0139] The weight fraction of unreacted molecules having a molecular weight higher than the weight average molecular weight of the acid-modified product (B) is within the above range. in If there is such a component, the proportion of unreacted molecules, particularly high molecular weight unreacted molecules which are poorly dispersible in water, decreases, and component (B) becomes more easily dispersed uniformly in water, which is preferable.

[0140] It is preferable that the component (B) according to the present invention further satisfies the following (B7). (B7) No melting point is observed. It is preferable that component (B) has no observed melting point in differential scanning calorimetry (DSC). Here, "no observed melting point (Tm)" means that the heat of fusion (ΔH) (unit: J / g) measured by differential scanning calorimetry (DSC) is not substantially measured. "No substantially measured heat of fusion (ΔH)" means that no peak is observed in differential scanning calorimetry (DSC) or the observed heat of fusion is 1 J / g or less.

[0141] The melting point (Tm) and heat of fusion (ΔH) of component (B) are determined by performing differential scanning calorimetry (DSC) and analyzing the DSC curve with reference to JIS K7121 when the component is cooled to -100°C and then heated to 150°C at a heating rate of 10°C / min. If no melting point is observed, this means that component (B) has low crystallinity, does not increase in viscosity, does not become solid, and has excellent dispersibility in water.

[0142] The component (B) may be used alone or in combination of two or more. <Aqueous dispersion composition> The aqueous dispersion composition of the present invention is the acid-modified ethylene-α-olefin copolymer. thing The content of (B) is in the range of 0.01 to 50% by mass, preferably 0.05 to 30% by mass.

[0143] The aqueous dispersion composition of the present invention preferably has a viscosity of 15 mPa·s or more, more preferably in the range of 20 to 200 mPa·s, even more preferably in the range of 30 to 200 mPa·s, particularly preferably in the range of 60 to 200 mPa·s, and most preferably in the range of 100 to 200 mPa·s. When the aqueous dispersion composition has a viscosity in this range, the aqueous dispersion composition is excellent in spreading over the surface of a substrate when applied or coated onto the substrate, and dripping is unlikely to occur, which is preferable since it provides excellent coating properties on the substrate.

[0144] The aqueous dispersion composition of the present invention is characterized in that the acid-modified ethylene / α-olefin copolymer forms the aqueous dispersion composition. thingThe average particle size of the dispersed particles (B) is preferably 100 nm or less, more preferably in the range of 10 to 95 nm, even more preferably in the range of 10 to 60 nm, particularly preferably in the range of 20 to 40 nm, and most preferably in the range of 20 to 30 nm. If the average particle size of the dispersed particles is larger than the above range, the particles tend to separate, which is not preferable from the viewpoint of stability. If the average particle size of the dispersed particles is smaller than the above range, the interaction between the particles becomes strong, and the viscosity of the aqueous dispersion composition tends to increase, which is not preferable because it is difficult to spread on the surface of the substrate. In other words, if the average particle size of the dispersed particles is in the above range, it is preferable because the stability of the aqueous dispersion composition is excellent and the coating property on the substrate is also excellent.

[0145] [Method of measuring average particle size] The average particle size in the present invention refers to the diameter of the particles when the cumulative volume is 50% when the total volume is 100%, and can be measured using a dynamic light scattering particle size distribution measuring device or a Nanotrac particle size distribution measuring device. In the present invention, the average particle size of the particles in the dispersion liquid was measured using a Nanotrac WAVE2-EX150 (manufactured by MicrotracBEL).

[0146] In addition, the water dispersion composition of the present invention being excellent in stability means that the water dispersion composition maintains a good dispersion state when stored under room temperature conditions. In the present invention, the stability of the aqueous dispersion composition was evaluated by placing the aqueous dispersion composition in a transparent cylindrical glass container having a length of 120 mm and a diameter of 40 mm, leaving it at rest at 23° C. for 15 hours, and then visually checking for the presence or absence of separation.

[0147] The water content of the aqueous dispersion composition of the present invention is preferably from 50 to 99.99% by mass, and more preferably from 60 to 99.95% by mass. The aqueous dispersion composition of the present invention is the acid-modified ethylene-α-olefin copolymer. thing In addition to (B), the composition may contain various additives such as surfactants, corrosion inhibitors, antioxidants, animal and vegetable oils or their fatty acid esters, synthetic lubricating oils, waxes, inorganic powders, etc. The additives may be used alone or in combination of two or more.

[0148] As the surfactant, various surfactants such as anionic, cationic, and nonionic surfactants can be used. For example, alkylene oxide adducts of nonylphenol, alkylene oxide adducts of linear higher alcohols having 12 to 18 carbon atoms, alkylene oxide adducts of higher amines, polyoxyethylene adducts of fatty acids such as castor oil, alkylene oxide adducts of fatty acid amides, alkyl sulfates, tamol type, tetraalkylammonium salts, and alkyl betaines can be exemplified. When a surfactant is used, the amount of the surfactant added is preferably 0.1 to 20% by mass, more preferably 0.5 to 10% by mass, in the aqueous dispersion composition.

[0149] Examples of the corrosion inhibitor include sodium nitrite, sodium benzoate, triethanolamine salts, etc. When a corrosion inhibitor is used, the amount of the corrosion inhibitor added is preferably 0.01 to 10% by mass, and more preferably 0.1 to 5% by mass in the aqueous dispersion composition.

[0150] The antioxidant may be a phenolic compound such as 2,6-di-t-butyl-4-methylphenol or an amine compound. The amount of the antioxidant added is preferably 0 to 3% by mass in the aqueous dispersion composition.

[0151] Examples of the animal and vegetable oils include mineral oil, rapeseed oil, soybean oil, coconut oil, palm oil, beef tallow, lard, etc. Examples of the synthetic lubricating oils include polyalphaolefin, polybutadiene, polyisobutylene, various ester oils, etc.

[0152] Examples of waxes that can be used include synthetic waxes such as polyethylene wax and polypropylene wax, oxides and acid-modified products of these synthetic waxes, and natural waxes such as carnauba, montan, and beeswax, provided that the dispersibility in water and adhesion to the mold are not adversely affected.

[0153] Inorganic powders include talc and mica.、 sticky soil , organic clay, boronite Ride Examples of the inorganic fillers include mortar, sericite, calcium carbonate, borate, alumina, titanium oxide, sodium bicarbonate, zirconium oxide, graphite, carbon black, and diamond powder.

[0154] Other components that may be used in combination include silicone compounds such as silicone, dimethyl silicone, alkyl-modified silicone, and alkylaralkyl-modified silicone; zinc dialkyldithiophosphate (ZnDTP), molybdenum dialkyldithiophosphate (MoDTP), zinc dithiocarbamate (ZnDTC), molybdenum dithiocarbamate (MoDTC), phosphorus-based and sulfur-based extreme pressure agents, antifoaming agents, and preservatives to reduce friction.

[0155] <Method for producing aqueous dispersion composition> The aqueous dispersion composition of the present invention can be produced, for example, by dissolving water in an aqueous solution of the acid-modified ethylene / α-olefin copolymer. thing The method includes emulsifying (B) and the above-mentioned additives as appropriate by a normal method, such as manually or by using a stirrer, or by using an emulsifying machine such as a homomixer, a colloid mill, a line mixer, a homogenizer, etc. The water temperature during emulsification is preferably 40 to 99°C, more preferably 50 to 99°C.

[0156] Acid denaturation thing When morpholine is used in preparing the aqueous dispersion composition (B), the morpholine is acid-modified. thing The morpholine reacts with the polar group of (B) to stabilize the aqueous dispersion composition. thing (B) may be mixed in advance and reacted. Morpholine is acid-modified. thing It is preferable to add 1 to 50 parts by mass, more preferably 1 to 30 parts by mass, and particularly preferably 2 to 20 parts by mass, per 100 parts by mass of (B).

[0157] In the present invention, the acid-modified ethylene-α-olefin copolymer is thing(B) As , an arbitrary acid value, an apparent viscosity at 150°C, a weight average molecular weight, a molecular weight distribution, a weight fraction of unreacted molecules, and an acid-modified ethylene-α-olefin copolymer having a weight fraction of unreacted molecules having a molecular weight higher than the weight average molecular weight of the acid-modified ethylene-α-olefin copolymer (B). thing By using (B), it is possible to adjust the stability, viscosity, and average particle size of the aqueous dispersion composition without changing the equipment or conditions during emulsification.

[0158] In particular, the weight fraction of the unreacted molecules adjusted, and the weight fraction of the unreacted molecules having a molecular weight higher than the weight average molecular weight of the acid-modified ethylene-α-olefin copolymer (B) among the unreacted molecules, thing The method using (B) makes it possible to adjust the stability, viscosity and average particle size of the aqueous dispersion composition without changing the total amount of polar groups in the acid-modified ethylene-α-olefin copolymer (B), or the molecular weight and molecular weight distribution. Therefore, for example, the change in properties when the aqueous dispersion composition is applied or coated and dried is likely to be small, and the method is preferred as a method for producing an aqueous dispersion composition having stability, viscosity and average particle size suitable for various applications.

[0159] <Application> The aqueous dispersion composition of the present invention is not particularly limited in its application, and can be used as various resin or rubber polymer modifiers, modifier auxiliaries, softeners, gel modifiers, latex modifiers, other water-soluble resin modifiers, emulsification auxiliaries such as emulsion polymerization auxiliaries, lubricating oil additives, adhesives, dispersants, dispersion auxiliaries, printing inks, printing pastes, lacquers, inks, coating agents for food packaging, coating agents for flooring, coating agents for shoes, coating agents for automobiles, other water-based paints, finishing agents for papermaking, spinning, and textiles, metal processing oils such as cutting oils and drawing oils, various release agents such as die-casting release agents, heat sealing agents, and cosmetics, various modifiers, modifier auxiliaries, inks, paints, coating materials, adhesives, etc. The aqueous dispersion composition of the present invention can ensure good adhesion to substrates when used as a heat sealing agent, and has excellent dispersibility in water, and therefore can be particularly suitably used as a heat sealing agent. EXAMPLES

[0160] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. [Evaluation method] Example below , reference example In the comparative examples and the like, the physical properties of the ethylene / α-olefin copolymer (A), the acid-modified ethylene / α-olefin copolymer (B) and the aqueous dispersion composition were measured by the following methods.

[0161] 《Physical properties of ethylene-α-olefin copolymer (A)》 <Ethylene unit content (mol%) (A1)> Using a JASCO Fourier transform infrared spectrophotometer FT / IR-610 or FT / IR-6100, the 721 cm -1 Absorption near 1155 cm due to propylene skeletal vibration -1 Absorbance ratio with absorption near 155cm -1 / D721cm -1 ) was calculated, and the content (mass%) of the ethylene unit was calculated from a calibration curve (prepared using a standard sample according to ASTM D3900) prepared in advance. Next, the content (mol%) of the ethylene unit was calculated using the obtained content (mass%) of the ethylene unit according to the following formula.

[0162]

number

[0163] <Molecular weight (A3) and molecular weight distribution (A4)> The molecular weight and molecular weight distribution were measured using Tosoh Corporation's HLC-8320GPC as follows. As the separation column, TSKgel SuperMultiporeHZ-M (4 columns) were used, the column temperature was 40°C, the mobile phase was tetrahydrofuran (manufactured by Wako Pure Chemical Industries, Ltd.), the development speed was 0.35 ml / min, the sample concentration was 5.5 g / L, the sample injection amount was 20 microliters, and a differential refractometer was used as the detector. As the standard polystyrene, Tosoh Corporation's PStQuick MP-M was used. According to the general-purpose calibration procedure, the weight average molecular weight (Mw) and number average molecular weight (Mn) were calculated in terms of polystyrene molecular weight, and the molecular weight distribution (Mw / Mn) was calculated from these values.

[0164] <B value (A5)> The measurement solvent was o-dichlorobenzene / benzene-d6 (4 / 1 [vol / vol%]), the measurement temperature was 120 °C, the spectrum width was 250 ppm, the pulse repetition time was 5.5 seconds, and the pulse width was 4.7 μsec (45° pulse) measurement conditions (100MHz, JEOL ECX400P), or measurement temperature 120°C, spectrum width 250ppm, pulse repetition time 5.5 seconds, and pulse width 5.0 μsec (45° pulse) measurement condition (125MHz, Bruker Biospin AVANCEIIIcryo-500) 13 The C-NMR spectrum was measured, and the B value was calculated based on the following formula [1]. Peak assignment was performed with reference to the above-mentioned known literature.

[0165]

number

[0166] <Unsaturated bond amount (A6)> The measurement conditions were: o-dichlorobenzene-d4 as the measurement solvent, measurement temperature 120°C, spectrum width 20 ppm, pulse repetition time 7.0 seconds, and pulse width 6.15 μsec (45° pulse). 1 H-NMR spectrum (400MHz, JEOL ECX400P) was measured. The solvent peak (orthodichlorobenzene 7.1ppm) was used as the chemical shift standard, and the amount of unsaturated bonds per 1000 carbon atoms (units / 1000C) was calculated from the ratio of the integral value of the main peak observed at 0-3ppm to the peak derived from unsaturated bonds observed at 4-6ppm.

[0167] <Melting point> Using Seiko Instruments X-DSC-7000, about 8 mg of copolymer sample was placed in a simple sealed aluminum sample pan and placed in a DSC cell. The DSC cell was heated from room temperature to 150°C at 10°C / min under a nitrogen atmosphere, then held at 150°C for 5 minutes, then cooled at 10°C / min, and the DSC cell was cooled to -100°C (cooling down process). Next, after holding at -100°C for 5 minutes, the temperature was raised at 10°C / min, and the temperature at which the enthalpy curve obtained during the heating process showed a maximum value was taken as the melting point (Tm), and the sum of the endothermic heats associated with melting was taken as the heat of fusion (ΔH). If no peak was observed or the value of the heat of fusion (ΔH) was 1 J / g or less, the melting point (Tm) was considered not to be observed. The melting point (Tm) and heat of fusion (ΔH) were determined based on JIS K7121.

[0168] 《Physical properties of acid-modified ethylene-α-olefin copolymer (B)》 <Acid value (B1)> Mixed xylene:n - A precisely weighed copolymer sample was dissolved in a mixed solvent of butanol and ethanol in a mass ratio of 1:1 to obtain a sample solution. Next, this sample solution was titrated with a previously standardized N / 10 potassium hydroxide alcohol solution (7 g of special grade potassium hydroxide was added with 5 g of ion-exchanged water, and the volume was adjusted to 1 L (liter) with primary ethyl alcohol, and the titer was standardized to F with N / 10 hydrochloric acid and 1% phenolphthalein solution), and the titer was calculated from the neutralization amount according to the following formula.

[0169] Acid value (mgKOH / g) = (N / 10 KOH titration volume (ml) x F x 5.61) / (sample (g) x 0.01) Apparent Viscosity (B2) The apparent viscosity (Brookfield viscosity) at 150° C. was measured and calculated according to the method described in JIS K7117-1.

[0170] <Molecular weight (B3) and molecular weight distribution (B4)> The molecular weight and molecular weight distribution were measured using Tosoh Corporation's HLC-8320GPC as follows. As the separation column, TSKgel SuperMultiporeHZ-M (4 columns) were used, the column temperature was 40°C, the mobile phase was tetrahydrofuran (manufactured by Wako Pure Chemical Industries, Ltd.), the development speed was 0.35 ml / min, the sample concentration was 5.5 g / L, the sample injection amount was 20 microliters, and a differential refractometer was used as the detector. As the standard polystyrene, Tosoh Corporation's PStQuick MP-M was used. According to the general-purpose calibration procedure, the weight average molecular weight (Mw) and number average molecular weight (Mn) were calculated in terms of polystyrene molecular weight, and the molecular weight distribution (Mw / Mn) was calculated from these values.

[0171] Weight fraction of unreacted molecules (B5) The weight fraction of unreacted molecules was measured using an HPLC apparatus (Alliance e2695 Separations Module / 2414 RI Detector) manufactured by Waters Corporation as follows.

[0172] Mobile phase: Hexane Flow rate: 1ml / min Sample concentration: 1w / v% Sample injection volume: 20 μL Column: Normal phase column manufactured by Agilent Technologies, Inc. Column size: inner diameter 4.6 mm, length 250 mm Column packing material: Silica particles (particle size 5 μm) Detector: Differential refractometer In the examples of the present invention, the ethylene-propylene copolymer used in the production of the acid-modified ethylene-α-olefin copolymer (B) was used as a standard. The peak area (S0) (appearing in the region of 2 to 3.5 minutes) of the standard measured under the above conditions was compared with the peak area (S MD ) is determined by the following formula: Weight fraction of unreacted molecules = 100 × S MD / S 0

[0173] 〈 Weight fraction (B6) of unreacted molecules having a molecular weight higher than the weight average molecular weight of the acid-modified ethylene-α-olefin copolymer (B) among unreacted molecules contained in the acid-modified ethylene-α-olefin copolymer (B) The molecular weight of the unreacted molecules contained in the acid-modified ethylene-α-olefin copolymer (B) was determined by separating the unreacted molecules using a silica column and measuring the molecular weight using gel permeation chromatography (GPC). The separation of the unreacted molecules was carried out by filling a chromatographic tube with crushed silica gel (Wakogel C-300, manufactured by Wako Pure Chemical Industries, Ltd.) to a height of 5 cm, impregnating it with hexane, adding a solution in which 1 g of the acid-modified ethylene-α-olefin copolymer (B) was dissolved in 5 mL of hexane, and then adding 20 mL of hexane from the top, and collecting and drying about 10 mL of the solution eluted from the bottom of the chromatographic tube. The molecular weight of the separated unreacted molecules was measured using a Tosoh Corporation HLC-8320GPC as follows, and the weight fraction of unreacted molecules with a molecular weight higher than the weight average molecular weight of the acid-modified ethylene-α-olefin copolymer (B) was calculated. The separation columns used were TSKgel SuperMultiporeHZ-M (4 columns), the column temperature was 40°C, the mobile phase was tetrahydrofuran (manufactured by Wako Pure Chemical Industries, Ltd.), the development speed was 0.35 ml / min, the sample concentration was 5.5 g / L, the sample injection amount was 20 microliters, and a differential refractometer was used as the detector. The standard polystyrene used was PStQuick MP-M (manufactured by Tosoh Corporation). 。 [Production example of ethylene-α-olefin copolymer (A)] Ethylene / α-olefin copolymer (A) was produced according to the following polymerization example. The resulting ethylene / α-olefin copolymer (A) was hydrogenated as necessary by the following method.

[0174] <Hydrogenation operation> 100mL of hexane solution of 0.5% by mass Pd / alumina catalyst and 500mL of 30% by mass hexane solution of ethylene-α-olefin copolymer were placed in a 1L stainless steel autoclave, the autoclave was sealed, and the inside of the autoclave was replaced with nitrogen. The temperature was then raised to 140°C with stirring, and the inside of the system was replaced with hydrogen. The pressure was then raised to 1.5MPa with hydrogen, and the hydrogenation reaction was carried out for 15 minutes.

[0175] <Synthesis of metallocene compounds> [Synthesis Example 1] [Methylphenylmethylene(η 5 -cyclopentadienyl)(η 5 Synthesis of (2,7-di-t-butylfluorenyl)zirconium dichloride (i) Synthesis of 6-methyl-6-phenylfulvene Under a nitrogen atmosphere, 7.3 g (101.6 mmol) of lithium cyclopentadiene and 100 mL of dehydrated tetrahydrofuran were added to a 200 mL three-neck flask and stirred. The solution was cooled in an ice bath, and 15.0 g (111.8 mmol) of acetophenone was added dropwise. After stirring for 20 hours at room temperature, the resulting solution was quenched with a dilute aqueous hydrochloric acid solution. 100 mL of hexane was added to extract the soluble matter, and this organic layer was washed with water and saturated saline, and then dried over anhydrous magnesium sulfate. The solvent was then distilled off, and the resulting viscous liquid was separated by column chromatography (hexane) to obtain the target product (red viscous liquid).

[0176] (ii) Synthesis of methyl(cyclopentadienyl)(2,7-di-t-butylfluorenyl)(phenyl)methane In a nitrogen atmosphere, 2.01 g (7.20 mmol) of 2,7-di-t-butylfluorene and 50 mL of dehydrated t-butyl methyl ether were added to a 100 mL three-neck flask. While cooling in an ice bath, 4.60 mL (7.59 mmol) of n-butyllithium / hexane solution (1.65 M) was gradually added and stirred at room temperature for 16 hours. After adding 1.66 g (9.85 mmol) of 6-methyl-6-phenylfulvene, the mixture was heated and stirred under reflux for 1 hour. While cooling in an ice bath, 50 mL of water was gradually added, and the resulting two-layer solution was transferred to a 200 mL separatory funnel. After adding 50 mL of diethyl ether and shaking several times, the aqueous layer was removed, and the organic layer was washed three times with 50 mL of water and once with 50 mL of saturated saline. After drying with anhydrous magnesium sulfate for 30 minutes, the solvent was distilled off under reduced pressure. When a small amount of hexane was added to the resulting solution, ultrasonic waves were applied to the solution, and a solid precipitated, which was collected and washed with a small amount of hexane. After drying under reduced pressure, 2.83 g of methyl(cyclopentadienyl)(2,7-di-t-butylfluorenyl)(phenyl)methane was obtained as a white solid.

[0177] (iii) [Methylphenylmethylene (η 5 -cyclopentadienyl)(η 5 Synthesis of (2,7-di-t-butylfluorenyl)zirconium dichloride Under a nitrogen atmosphere, 1.50 g (3.36 mmol) of methyl(cyclopentadienyl)(2,7-di-t-butylfluorenyl)(phenyl)methane, 50 mL of dehydrated toluene, and 570 μL (7.03 mmol) of THF (tetrahydrofuran) were added to a 100 mL Schlenk flask in this order. While cooling in an ice bath, 4.20 mL (6.93 mmol) of n-butyllithium / hexane solution (1.65 M) was gradually added, and the mixture was stirred at 45 ° C for 5 hours. The solvent was distilled off under reduced pressure, and 40 mL of dehydrated diethyl ether was added to obtain a red solution. While cooling in a methanol / dry ice bath, 728 mg (3.12 mmol) of zirconium tetrachloride was added, and the mixture was stirred for 16 hours while gradually raising the temperature to room temperature, resulting in a red-orange slurry. The solid obtained by distilling off the solvent under reduced pressure was brought into a glove box, washed with hexane, and then extracted with dichloromethane. After the solvent was removed under reduced pressure and the mixture was concentrated, a small amount of hexane was added and the mixture was left at -20°C, whereupon a reddish-orange solid precipitated. This solid was washed with a small amount of hexane and then dried under reduced pressure to obtain [methylphenylmethylene(η 5 -cyclopentadienyl)(η 5 1.20 g of 2,7-di-t-butylfluorenyl)]zirconium dichloride was obtained.

[0178] [Synthesis Example 2] [Ethylene(η 5 -cyclopentadienyl)(η 5 Synthesis of (2,7-di-t-butylfluorenyl)zirconium dichloride [Ethylene(η 5 -cyclopentadienyl)(η 5

[0046] The (-2,7-di-t-butylfluorenyl)]zirconium dichloride was synthesized by the method described in Japanese Patent No. 4367687.

[0179] <Polymerization Example 1> 760 ml of heptane and 120 g of propylene were charged into a 2 L stainless steel autoclave that had been thoroughly purged with nitrogen, and the temperature inside the system was raised to 150°C. Then, 0.85 MPa of hydrogen and 0.19 MPa of ethylene were fed to adjust the total pressure to 3 MPaG. Next, 0.4 mmol of triisobutylaluminum, [methylphenylmethylene (η 5 -cyclopentadienyl)(η 5 0.0002mmol of 1,2,7-di-t-butylfluorenyl)]zirconium dichloride and 0.002mmol of N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate were injected with nitrogen, and polymerization was started by changing the stirring speed to 400 rpm. Then, the total pressure was kept at 3MPaG by continuously feeding only ethylene, and polymerization was carried out at 150°C for 5 minutes. After the polymerization was stopped by adding a small amount of ethanol to the system, unreacted ethylene, propylene, and hydrogen were purged. The obtained polymer solution was washed three times with 1000ml of 0.2mol / L hydrochloric acid and then three times with 1000ml of distilled water, dried over magnesium sulfate, and the solvent was distilled off under reduced pressure. The obtained polymer was dried under reduced pressure at 80°C for 10 hours, and 60.9g of ethylene-propylene copolymer was obtained. Furthermore, this ethylene-propylene copolymer was subjected to a hydrogenation operation.

[0180] By the above operations, the ethylene-propylene copolymer (A-1) shown in Table 1 was obtained. The analytical results of the obtained ethylene-propylene copolymer (A-1) are shown in Table 1. <Polymerization Example 2> 710 mL of heptane and 145 g of propylene were charged into a 2 L stainless steel autoclave that had been thoroughly purged with nitrogen, and the temperature inside the system was raised to 150°C. Then, 0.40 MPa of hydrogen and 0.27 MPa of ethylene were fed to adjust the total pressure to 3 MPaG. Next, 0.4 mmol of triisobutylaluminum, [methylphenylmethylene (η 5 -cyclopentadienyl)(η 50.0001mmol of 1,2,7-di-t-butylfluorenyl)zirconium dichloride and 0.001mmol of N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate were injected with nitrogen, and the polymerization was started by changing the stirring speed to 400 rpm. Then, the total pressure was kept at 3MPaG by continuously feeding only ethylene, and the polymerization was carried out at 150°C for 5 minutes. After the polymerization was stopped by adding a small amount of ethanol to the system, the unreacted ethylene, propylene, and hydrogen were purged. The obtained polymer solution was washed three times with 1000mL of 0.2mol / l hydrochloric acid, then three times with 1000mL of distilled water, dried over magnesium sulfate, and the solvent was distilled off under reduced pressure. The obtained polymer was dried overnight under reduced pressure at 80°C to obtain 52.2g of ethylene-propylene copolymer. Furthermore, this ethylene-propylene copolymer was subjected to a hydrogenation operation.

[0181] By the above operations, the ethylene-propylene copolymer (A-3) shown in Table 1 was obtained. The analytical results of the obtained ethylene-propylene copolymer (A-3) are shown in Table 1. In addition, ethylene-propylene copolymers (A-2), (A-4), and (A-5) obtained by a method using a vanadium catalyst containing a vanadium compound and an organoaluminum compound in the same manner as described in JP-B-2-1163 and JP-B-2-7998 were used in the examples. The analytical results of the ethylene-propylene copolymers (A-2), (A-4), and (A-5) used are shown in Table 1.

[0182] <Production Example 1> Ethylene-propylene copolymer (A-6) was obtained by mixing 95.5% by weight of ethylene-propylene copolymer (A-1) and 4.5% by weight of ethylene-propylene copolymer (A-3). The analytical results of the obtained ethylene-propylene copolymer (A-6) are shown in Table 1.

[0183] <Production Example 2> Ethylene-propylene copolymer (A-7) was obtained by mixing 94.3% by weight of ethylene-propylene copolymer (A-2) and 5.7% by weight of ethylene-propylene copolymer (A-4). The analytical results of the obtained ethylene-propylene copolymer (A-7) are shown in Table 1.

[0184] <Production Example 3> Ethylene-propylene copolymer (A-8) was obtained by mixing 91.4% by weight of ethylene-propylene copolymer (A-2), 4.3% by weight of ethylene-propylene copolymer (A-4), and 4.3% by weight of ethylene-propylene copolymer (A-5). The analytical results of the obtained ethylene-propylene copolymer (A-8) are shown in Table 1.

[0185] [Table 1] [Production of acid-modified ethylene-α-olefin copolymer (B)] The ethylene-propylene copolymers (A-6) to (A-8) shown in Table 1 were used to carry out graft modification with a graft component.

[0186] <Basic operations for producing olefin polymer compositions> A reactor equipped with a stirrer, a nitrogen inlet tube, a water-cooled condenser, a thermometer, a maleic anhydride supply device, and a radical generator supply device, is charged with any one of the ethylene-propylene copolymers (A-6) to (A-8), and the temperature is raised. After that, Nitrogen was introduced into the reactor at 120°C to purge the oxygen in the system, and the temperature in the system was maintained at 160°C. Then, maleic anhydride Wako special grade (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., liquid at about 70°C) and di-t-butyl peroxide Perbutyl D (manufactured by Nippon Oil & Fats Co., Ltd.) were supplied to the reactor for a predetermined time at a predetermined speed and under a predetermined stirring speed, and after the supply was completed, the reactor was further kept at 160°C for 1 hour and stirring was continued. Next, the temperature in the reactor was further increased to 175°C, and after depressurizing the system, unnecessary components (unreacted maleic anhydride and decomposition products of di-t-butyl peroxide, etc.) were removed under reduced pressure and nitrogen flow conditions.

[0187] <Modification Examples 1-10> According to the basic procedure for producing the olefin polymer composition, ethylene propylene was produced under various production conditions disclosed in Table 2. copolymer Acid-modified products (B-1) to (B-10) were produced. The results are shown in Table 2.

[0188] <Production Example 4> 95% by mass of the ethylene-propylene copolymer acid-modified product (B-7) and 5% by mass of the ethylene-propylene copolymer (A-6) were uniformly mixed to obtain an ethylene-propylene copolymer acid-modified product (B-11). 1 The analysis results are shown in Table 3.

[0189] <Production Example 5> 95% by mass of the acid-modified ethylene-propylene copolymer (B-7) and 5% by mass of the ethylene-propylene copolymer (A-3) were uniformly mixed to obtain an acid-modified ethylene-propylene copolymer (B-12). The analytical results of the acid-modified ethylene-propylene copolymer (B-12) obtained are shown in Table 3.

[0190] <Production Example 6> The ethylene-propylene copolymer acid-modified product (B-10) (80% by mass) and the ethylene-propylene copolymer (A-6) (20% by mass) were uniformly mixed to obtain an ethylene-propylene copolymer acid-modified product (B-13). The analytical results of the obtained ethylene-propylene copolymer acid-modified product (B-13) are shown in Table 3.

[0191] [Table 2]

[0192] [Table 3] <Aqueous dispersion composition> [ reference Example 1] 41.6 g of ethylene-propylene copolymer acid modified product (B-1) and 10.4 g of polyoxyethylene alkyl ether Emulgen 1108 (manufactured by Kao Corporation) were placed in a 500 mL round bottom flask equipped with a stirrer, and the mixture was heated to 96°C while stirring at a stirring speed of 50 rpm. Next, a solution of 7.5 g of morpholine grade 1 (manufactured by Kanto Chemical Co., Ltd.) and 10.0 g of pure water was added, and the mixture was reacted for 30 minutes at a stirring speed of 250 rpm. Then, 134 g of hot water at 97°C was added, and the mixture was stirred for 60 minutes at a stirring speed of 500 rpm, and then cooled for 30 minutes at a stirring speed of 250 rpm to obtain an aqueous dispersion composition. The stability, viscosity, and average particle size of the obtained aqueous dispersion composition were evaluated according to the following method. The analysis results of the obtained aqueous dispersion composition are shown in Table 4.

[0193] Example 2 ,4 ~ 9, and Reference Example 3, 10] reference The same procedure as in Example 1 was repeated except that the acid-modified ethylene-propylene copolymer used was changed to that shown in Table 4. reference An aqueous dispersion composition was obtained in the same manner as in Example 1. The analytical results of the obtained aqueous dispersion composition are shown in Table 4.

[0194] [Comparative Examples 1 and 2] reference The same procedure as in Example 1 was repeated except that the acid-modified ethylene-propylene copolymer used was changed to that shown in Table 4. reference An aqueous dispersion composition was obtained in the same manner as in Example 1. The stability of the obtained aqueous dispersion composition was evaluated, and as a result, separation occurred, and therefore the viscosity and average particle size could not be measured. [Stability of Water Dispersion Composition] The stability of the aqueous dispersion composition was evaluated by placing the aqueous dispersion composition in a transparent cylindrical glass container having a length of 120 mm and a diameter of 40 mm, and visually observing whether separation occurred after leaving the composition at rest for 15 hours at 23° C. The aqueous dispersion composition in the glass container was evaluated as having no separation when the turbidity was uniform, and as having a difference in the turbidity in the height direction when separation was observed.

[0195] [Viscosity of Water Dispersion Composition] The viscosity of the aqueous dispersion composition was measured at 23° C. using a B-type viscometer TVB-10M (manufactured by Toki Sangyo Co., Ltd.) For the measurement, the sample used for evaluating the stability of the aqueous dispersion composition was used as it was.

[0196] [Average particle size of aqueous dispersion composition] The average particle size of the aqueous dispersion composition was measured using Nanotrac WAVE2-EX150 (manufactured by MicrotracBEL). For the measurement, 1 g of the sample for evaluating the stability of the aqueous dispersion composition was weighed into a polypropylene cup, and the pure water The measurement was performed after diluting with 10 g. From the measurement results obtained, the average particle size was determined as the diameter of the particles when the cumulative volume was 50% when the total volume was 100%.

[0197] [Table 4] Examples of Water Dispersion Compositions 2,4 ~ 9, and Reference Examples 1, 3, Comparing Example 10 with Comparative Examples 1 and 2, it can be seen that the aqueous dispersion composition using an acid-modified ethylene-propylene copolymer having a low weight fraction of unreacted molecules is excellent in stability. It can also be seen that the aqueous dispersion composition using an acid-modified ethylene-propylene copolymer having a low ratio of high molecular weight components in the unreacted molecules is excellent in stability. 2,4 ~ 9, and Reference Examples 1, 3, Among the above 10, an aqueous dispersion composition using an acid-modified ethylene-propylene copolymer having a low weight fraction of unreacted molecules and a small proportion of high molecular weight components in the unreacted molecules is more preferred because it has a small average particle size and a high viscosity, and therefore is more stable. In addition, when applied to a substrate, it is expected to have good substrate coating properties such as excellent adhesion and little dripping. [Industrial Applicability]

[0198] The aqueous dispersion composition, the method for producing the aqueous dispersion composition, and the acid-modified ethylene-α-olefin copolymer of the present invention provide an aqueous dispersion having excellent stability and excellent coating properties on substrates, and therefore can be used for modifiers, modifier auxiliaries, softeners, gel modifiers, latex modifiers, other water-soluble resin modifiers, emulsification auxiliaries such as emulsion polymerization auxiliaries, lubricating oil additives, adhesives, dispersants, dispersion auxiliaries, printing inks, printing pastes, lacquers, inks, coating agents for food packaging materials, coating agents for flooring materials, coating agents for shoes, coating agents for automobiles, other water-based paints, finishing agents for papermaking, spinning, and textiles, metal processing oils such as cutting oils and drawing oils, various release agents such as die-casting release agents, heat sealing agents, and various modifiers, modifier auxiliaries, inks, paints, coating materials, adhesives, etc., including cosmetics. Among these, the composition is particularly suitable for use as a heat sealing agent, since it has excellent stability and excellent coating properties on substrates.

Claims

1. The aqueous dispersion composition is characterized by comprising an acid-modified ethylene / α-olefin copolymer (A) that satisfies the following (A1) to (A6), and an acid-modified ethylene / α-olefin copolymer (B) that satisfies the following (B1) to (B6) in an amount in the range of 0.01 to 50 mass %. (A1) The content of ethylene units is in the range of 30 to 85 mol %. (A2) Kinematic viscosity at 100 ° C. is 10 to 5,000 mm 2 / s range. (A3) The weight average molecular weight, as calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) is in the range of 1,000 to 50,000. (A4) The molecular weight distribution (Mw / Mn) measured by gel permeation chromatography (GPC) and calculated as polystyrene is 2.5 or less. (A5) The B value represented by the following formula [1] is 1.1 or more. [0010] [In formula [1], P E represents the mole fraction of ethylene units, and P O represents the molar fraction of α-olefin units, and P OE indicates the molar fraction of ethylene / α-olefin chains among all dyad chains. (A6) 1 The amount of unsaturated bonds as measured by H-NMR is less than 0.5 per 1,000 carbon atoms. (B1) The acid value is in the range of 1 to 300 mg KOH / g. (B2) The apparent viscosity at 150°C is in the range of 1 to 1,000 cPs. (B3) The weight average molecular weight, as calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) is in the range of 1,000 to 50,000. (B4) The molecular weight distribution (Mw / Mn) of the molecular weight, calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) is 2.5 or less. (B5) The weight fraction of unreacted molecules as measured by high performance liquid chromatography (HPLC) is 54% or less. (B6) Among unreacted molecules contained in the acid-modified product (B), the weight fraction of unreacted molecules having a molecular weight higher than the weight average molecular weight of the acid-modified product (B) obtained in terms of polystyrene, as measured by gel permeation chromatography (GPC), is 18.5% or less.

2. The aqueous dispersion composition according to claim 1, wherein the acid-modified product (B) is a copolymer obtained by modifying the ethylene / α-olefin copolymer (A) with at least one selected from maleic acid and maleic anhydride.

3. 3. The aqueous dispersion composition according to claim 1, wherein the aqueous dispersion composition has a viscosity of 15 mPa·s or more.

4. 4. The aqueous dispersion composition according to claim 1, wherein the average particle size of dispersed particles in the aqueous dispersion composition is 100 nm or less.

5. A method for producing the aqueous dispersion composition described in any one of claims 1 to 4, comprising a step of emulsifying water and the acid-modified product (B).

6. The acid-modified ethylene / α-olefin copolymer (B) is an acid-modified ethylene / α-olefin copolymer (A) that satisfies the following (A1) to (A6), and is characterized in that it satisfies the following (B1) to (B6). (A1) The content of ethylene units is in the range of 30 to 85 mol %. (A2) Kinematic viscosity at 100 ° C. is 10 to 5,000 mm 2 / s range. (A3) The weight average molecular weight, as calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) is in the range of 1,000 to 50,000. (A4) The molecular weight distribution (Mw / Mn) measured by gel permeation chromatography (GPC) and calculated as polystyrene is 2.5 or less. (A5) The B value represented by the following formula [1] is 1.1 or more. [0025] [In formula [1], P E represents the mole fraction of ethylene units, and P O represents the molar fraction of α-olefin units, and P OE indicates the molar fraction of ethylene / α-olefin chains among all dyad chains. (A6) 1 The amount of unsaturated bonds as measured by H-NMR is less than 0.5 per 1,000 carbon atoms. (B1) The acid value is in the range of 1 to 300 mg KOH / g. (B2) The apparent viscosity at 150°C is in the range of 1 to 1,000 cPs. (B3) The weight average molecular weight, as calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) is in the range of 1,000 to 50,000. (B4) The molecular weight distribution (Mw / Mn) of the molecular weight, calculated in terms of polystyrene, measured by gel permeation chromatography (GPC) is 2.5 or less. (B5) The weight fraction of unreacted molecules as measured by high performance liquid chromatography (HPLC) is 54% or less. (B6) Among unreacted molecules contained in the acid-modified product (B), the weight fraction of unreacted molecules having a molecular weight higher than the weight average molecular weight of the acid-modified product (B) obtained in terms of polystyrene, as measured by gel permeation chromatography (GPC), is 18.5% or less.

7. The acid-modified ethylene / α-olefin copolymer (B) according to claim 6, which is a copolymer obtained by modifying the ethylene / α-olefin copolymer (A) with at least one selected from maleic acid and maleic anhydride.

Citation Information

Patent Citations

  • Aqueous mold parting material for die casting

    JP1989053727A

  • High crystallinity olefin-dispersed fluid

    JP2015052124A

  • Water dispersion composition

    JP2016102157A